GBIF Occurrence Download - Occdownload Gbif.Org (The Global Biodiversity Information Facility, 2015)
A dataset containing 539481243 species occurrences available in GBIF matching the query: All data. The dataset includes 539481243 records from 13032 constituent datasets: 242 records from Schieferbrüche. 11371 records from Herbario Museo de La Salle Bogotá (MLS). 14760 records from Outer Hebrides Biological Recording Project - OHBRP Insects Dataset - Outer Hebrides. 353326 records from UCJEPS TAPIR Provider. 12 records from Ohemoor (Hamburg/Norderstedt). 2 records from Stadtrand Berlin - Altglienicke/ Was krabbelt auf unserem Abenteuerspielplatz?. 140 records from BIRDRACE Guckers Offenbach. 103 records from BIRDRACE federleser. 121 records from Owere Fiddel. 202 records from Total foraminifera counts from multinet M31/3_MSN900. 80 records from Total foraminifera counts from M35/1_MSN1062. 40 records from Plasm bearing foraminifera counts from M35/1_MSN1057. 89 records from Total foraminifera counts of multinet M10/2_MSN298. 64 records from Total foraminifera counts of multinet M42/3_MSN1369. 59 records from Granulometry and foraminiferal content of sediment core PI-88-AR_P7. 3 records from Large protozoa abundance measured on concentrated water bottle samples at station PS58/038-7. 58 records from Microzooplankton (larger protists and small copepods) abundance measured on concentrated water bottle samples at station PS65/570-14. 122 records from Abundance of planktic foraminifera at CTD station PS55/043. 125 records from Abundance of planktic foraminifera at CTD station PS55/082-1. 6 records from Microzooplankton abundance and biomass at station NBP97-03-09-1. 159 records from Phytoplankton abundance at station CD47_0606C#7. 7868 records from University of Amsterdam (NL) - Páramo Vegetation Research, Rabanal, Guerrero and Villa de Leyva paramo complex, Colombia. 344 records from Butterberg, Dardesheim. 23 records from Tümpel Schulbiologiezentrum. 9302 records from Ants from the Paraguayan dry Chaco. 35 records from Neoniphon pencei, a new species of holocentrid (Teleostei: Beryciformes) from Rarotonga, Cook Islands. 980 records from (Table AT7) Planktonic foraminiferal stratigraphy of ODP Hole 182-1132B. 511 records from Coleoptera of Swierklaniec Forest. 2805 records from Fundación Miguel Lillo - Colección Mamíferos. 4 records from A new carpenter ant, Camponotus parabarbatus (Hymenoptera: Formicidae) from India. 9396 records from RSPB - White-tailed eagle reintroduction in Scotland - Sightings data (RSPB/SNH). 90 records from Taxonomy of the plesiolebiasine killifish genera Pituna, Plesiolebias and Maratecoara (Teleostei: Cyprinodontiformes: Rivulidae), with descriptions of nine new species.. 4857 records from University of Alberta Museums, Entomology Collection. 63 records from Polypterus mokelembembe, a new species of bichir from the central Congo River basin (Actinopterygii: Cladistia: Polypteridae).. 2000 records from Colección Científica de Referencia Zoológica del Chocó- Herpetología. 4286 records from Inventaire National du Patrimoine Naturel : Atlas de la flore de Lorraine. 2 records from (Supplement Table 3) Percentage cover abundance of plants recorded at the Fell-field Site on Disko Island. 520 records from Lepidoptera collection (EL) of the Muséum national d'Histoire naturelle (MNHN - Paris). 1 records from Die vom k. k. Oberartze Herrn Dr. Justyn Karlinski im Jahre 1887 in Bosnien, der Herzegowina und in Novibazar gesammelten Myriopoden. 74752 records from Mammals collection (ZM) of the Muséum national d'Histoire naturelle (MNHN - Paris). 8579 records from The atlas of breeding birds in Małopolska. 60163 records from Rapid Assessment Program (RAP) Biodiversity Survey Database. 77 records from Terrestrial gastropods of Srebarna Nature Reserve, North-Eastern Bulgaria (Gastropoda). 9 records from Microzooplankton abundance and biomass at station TT043_2-1. 11 records from Microzooplankton abundance and biomass at station TT045_2-1. 97 records from DMNH Eggs. 1352 records from (Figure 9) Distribution of Cretaceous planktonic foraminifers and associated organisms from DSDP Hole 77-536. 113 records from Studies on species of Holarctic Pardosa groups (Araneae, Lycosidae). VII. The Pardosa tesquorum group. 1020718 records from Consortium of California Herbaria. 36432 records from RSPB - Corncrake national surveys - raw data (SCARABBS). 146 records from A taxonomic revision of the catshark genus Poroderma Smith, 1837 (Chondrichthyes: Carcharhiniformes: Scyliorhinidae).. 26152 records from Herts Bird Club - Hertfordshire Breeding Bird Atlas : 1967-1973. 26624 records from Monitoring data from the federal state Bavaria (Germany). 33 records from Relative abundance of Florisphaera profunda in ODP Hole 121-758C. 45 records from Sediment age, abundance of planktonic foraminifera shells, degree of their dissolution, percentage of benthic foraminifera in total foram fauna, Core GC-11, Sea of Okhotsk. 27167 records from Bird tissue collection, Natural History Museum, University of Oslo. 1702 records from (Table 1) Benthic foraminifera species observed in the Quaternary samples from DSDP Hole 95-612. 3268 records from (Table 1) Distribution of early Eocene to early middle Eocene benthic foraminifera in DSDP Hole 93-605. 1 records from Flora of Suriname, volume VI, part I. 1150 records from RSPB - Great Yellow Bumblebee sightings data in the UK, 1990 onwards (RSPB, BBCT, HBRG).. 1 records from Hoplophora crinita. 23046 records from Hemipteran specimens of Iwate Prefectural Museum. 57 records from verschiedene Kleingewässer um Oldenburg/Holstein. 473 records from (Table 1) Foraminifera abundance of ODP Hole 162-985A sediments. 105 records from (Table 1) Occurrence of Early Cretaceous foraminifers and radiolarians in ODP Hole 130-807C. 58 records from Weidewirtschaft. 53 records from Bad Bodenteicher Heide. 1346 records from EcoRecord - Fungi & Lichen records held by EcoRecord for the Birmingham and the Black Country area collated prior to March 2013. 81 records from Stadtpark Schmölln. 21 records from Tauchen und Meer 02. 112 records from Kaniswall/ Gosener Wiesen an der Spree. 75 records from BIRDRACE Die Kartoffelsäcke. 17 records from Nachtinsekten am Muldenufer. 124 records from Benthic foraminifera assemblage in sediment core BBLL3_MC2. 108 records from Assemblage of living benthic foraminifera in sediment profile GeoB4906-5. 83 records from Abundance of living benthic foraminifera in sediment core CD86_02_BC5. 267 records from Assemblage of living benthic foraminifera in sediment core GeoB3713-1. 52 records from Total foraminifera counts of multinet M21/4_MSN713. 56 records from Total foraminifera counts of multinet M21/5_MSN741. 133 records from Total foraminifera counts of multinet M42/3_MSN1363. 95 records from Plasm bearing foraminifera counts of multinet M21/2_MSN624. 88 records from Plasm bearing foraminifera counts of multinet M21/2_MSN627. 70 records from Plasm bearing foraminifera counts of multinet PO247/2_MSN1387. 13 records from Content of coarse fraction and G. menardii in sediment corev V25-52. 5 records from Trap data GBZ4, 696 m. 9 records from (Fig. 3) Pollen analysis of the Bosque de Avicennia core. 299 records from Total foraminifera counts of multinet M21/3_MSN662. 102 records from Plasm bearing foraminifera counts of multinet PO247/2_MSN1380. 13 records from Planktic foraminifera counts of multinet PS31/002. 368 records from RSPB - Ring ouzel national sample survey in the UK in 1999 (SCARABBS). 17 records from Dinoflagellate cysts of sediment core IOW211660-6. 43 records from Diatom assamblage in samples from sediment trap NB6. 195 records from National Trust - Greater Horseshoe Bat records on National Trust properties in the South West. 6 records from Microzooplankton abundance and biomass at station TT043_13-1. 2 records from Microzooplankton abundance and biomass at station TT050_19-3. 3 records from Microplankton counts and carbon biomass at station TT011_11-CTD142. 783 records from Phytoplankton abundance in surface water during cruise CD61. 165 records from Phytoplankton abundance during Lev Titov cruise LT91. 1045745 records from Herbarium of The New York Botanical Garden. 101 records from Relative abundance of coccosphere-units of sediment core GIK23411-5. 12 records from Nannofossil abundance of Hole 7-63B. 4 records from Abundance of broken diatom frustules measured on water bottle samples at station PS58/043-2. 810 records from Planktic foraminifera counts of sediment core V04-8. 65 records from Planktic foraminifera counts of sediment core V28-128. 638 records from MNA - Sezione di Genova - (Marine Biological Samples). 58 records from (Table 4) Relative abundance of selected benthic foraminifera in ODP Hole 104-642D. 1805 records from (Table 2) Occurrence of Oligocene to Pleistocene benthic foraminifers in ODP Site 121-756. 74 records from Occurrence of mammalia relicts at site l´Abri de Campalou. 20 records from Abundance and carbon biomass of phytoplankton at station TT012_5-CTD88. 1698 records from MNA Italica 2004_Rauschert dredge_Ross_sea_Mollusca_lgp. 102 records from Raus in die Natur. 5 records from Nannofossil abundance of Hole 10-85. 14 records from Nannofossil abundance of Hole 7-64. 3 records from Nannofossil abundance of Hole 51-417D. 17619 records from Akita Prefectural Museum, Insect Collection. 138 records from RMT Trawl catch from the 1983/84 V5 ADBEX II voyage. 24 records from (Table 6) Distribution of Pleistocene to late Pliocene nannofossils in ODP Hole 108-660A. 162 records from (Table 5) Distribution of calcareous nannofossils from selected samples of ODP Hole 107-655A. 635 records from Distribución, estructura poblacional y variación genética de algunas especies de pinos en peligro de extinción en México. 2320 records from (Table 7) Distribution of planktonic foraminifera in the early Miocene to late Pliocene section of ODP Hole 149-899A. 8 records from Description of lithologic section units of IODP Hole 325-M0040A. 581051 records from Swiss National Butterflies Databank. 2440 records from Marine and Coastal Management - Seal Surveys (AfrOBIS). 84 records from E.C. Manning Park Collection. 1170 records from Colección de Cnidarios. 92 records from (UTC-MO) University of Tennessee - Molluscs Collection. 836 records from Visual Plants (144.41.33.158) - Botanical garden, University of Hohenheim, Germany. 806 records from Bulk components and planktonic foraminifera of sediment core GIK17748-2. 102 records from Muehlenbach bei Friesheim. 19 records from Microplankton abundance at Station MARCH-1997-GN36199704603MNB03 in the euphotic zone of the Aegean Sea in spring 1997. Part 2 - dinoflagellates. 77 records from Occurrence of mammalia relicts at site Remetehegy. 1556 records from Planktic foraminifera abundance of Hole 7-64. 2 records from Range table from planktonic foraminifers in ODP Hole 139-855D. 18 records from Abundance, biovolume and biomass of heterotrophic dinoflagellates at station TT007_5-CTD56. 9 records from Phytoplankton abundance at station Casma_2003-06-04_2, Casma, Peru. 1677 records from Distribution of planktonic foraminifera in DSDP Hole 31-296 (Table III). 827 records from Schatzinsel Norderney. 24 records from Liether Park (LMS), 6b. 2 records from Nannofossil abundance of Hole 9-79. 56 records from Nannofossil abundance of Hole 82-558A. 25 records from Ostracoda abundance of Hole 34-320. 1892 records from Physical properties and geochemical composition of sediment cores PTA02-04, PTA03-12 and PTA03-13 from Laguna Potrok Aike, Patagonia. 20 records from Meiofauna abundance in sediment core 13200-024. 823 records from Planktic foraminifera counts of sediment core V17-165. 1298 records from Colección de Aves y Mamíferos del Valle de Cuatrociénegas, Coah., México (UANL). 1000 records from Plant (NHMK-PL). 1517 records from IBF Monitoring of Fungi. 311 records from (App 1) Relative contents of mass species of benthic foraminifera in Holocene sediments from Core ASV11-880-3. 11981 records from SMNK Mantid Collection. 118 records from (Table 3) Distribution of late Miocene to Pleistocene calcareous nannofossils in ODP Hole 105-647A. 8 records from Component analysis of TV-guided grab sampler GeoB10071-4. 24 records from (Table 1) Distribution of calcareous nannofossils at ODP Hole 125-781A. 76 records from (Table 1) Counts and concentrations of pollen, spores and dinoflagellate cysts in sediment core MD01-2378. 4 records from Neolamprologus devosi sp. n., a new riverine lamprologine cichlid (Teleostei, Cichlidae) from the lower Malagarasi River, Tanzania.. 7 records from Pseudomystus stenogrammus, a new species of bagrid catfish from Borneo (Teleostei, Bagridae).. 71 records from Nannofossil abundance of Hole 64-478. 4 records from Nannofossil abundance of Hole 9-81. 3 records from Nannofossil abundance of Hole 7-62. 15 records from Microfossil abundance of Hole 59-450. 11 records from Nannofossil abundance of Hole 55-431A. 8 records from Phytoplankton abundance measured on water bottle samples at station PS65/587-1. 4804 records from North Ayrshire Countryside Ranger Service - Species within North Ayrshire from 1984 - Present. 1610 records from (Appendix A) Stratigraphic range and relative abundance of Paleogene planktonic foraminifera in ODP Hole 120-747A. 28 records from Admiralty Bay Benthos Diversity Data Base (ABBED). Pycnogonida.. 148 records from Polychaetes in surface sediments off Sylt collected during Heincke cruise HE293. 230 records from (Table 2) Range chart for planktonic foraminifers from ODP Hole 111-677B. 2713 records from Relative abundances of planktonic foraminifera in ODP Site 121-758 (Table 1). 1024 records from (Appendix 1) Census data of planktic foraminiferal faunas together with estimates of mean annual SST for ODP Site 181-1119. 6724 records from Actualización de la base de datos del Herbario de la Universidad de Sonora (USON). 17355 records from Ibaraki Nature Museum,Lichen collection. 11 records from Description of lithologic section units of IODP Hole 325-M0056A. 287 records from Collection Odonata - SMF. 26721 records from Bird Observational Records. 7 records from (Table 4) Concentrations of PCBs and MeSO2-PCBs in adipose tissue of polar bears (Ursus maritimus) between 1991-2007. 115365 records from TTU Mammals Collection. 1122 records from (Figure 2) Stratigraphic distribution of planktonic foraminifera in the Neogene of ODP Hole 122-762B. 3998 records from Diversidad vegetal en un gradiente en la Sierra Madre Occidental: flora y vegetación de la Región de San Javier y Yécora, Sonora. 83 records from Phytoplankton abundance during Professor Vodyanitskiy cruise PV5. 880 records from Collection Paleobotanique de l'Universite Paris 6. 29 records from Potential indicator species of climate changes occurring in Québec, Part 1: the small brown lacewing fly Micromus posticus (Walker) (Neuroptera: Hemerobiidae). 811 records from U. S. National Parasite Collection's holdings from Robert L. Rausch. 1208 records from Cetacean Sightings Survey and Southern Ocean cetacean program. 59977 records from Institut Botanic de Barcelona, BC. 243 records from Memorial University Department of Biology Collection. 2042 records from Butterflies and Skippers of Alberta Project. 2016 records from Fish tissues, Division of Genomic Resources, UNM, Albuquerque, NM.. 1833 records from DSMZ Fungi. 313949 records from United States National Plant Germplasm System Collection. 1389 records from (Table T5) Planktonic foraminifera abundance of ODP Hole 170-1043A sediments. 6 records from Sediment properties of core CD86_09_PC. 150 records from Schulgarten Huttenheim (Philippsburg/Baden). 121 records from GEO-Hauptveranstaltung Bodden (Vilm). 207 records from Geo-Tag der Artenvielfalt Süßen Hornwiesen-Grundschule. 68 records from Microplankton abundance at Station MARCH-1998-GN36199804610MSB01 in the euphotic zone of the Aegean Sea in March 1998. Part 2 - dinoflagellates. 28 records from Microplankton abundance in the euphotic zone of the Aegean Sea at Station MARCH-94-GN3619940280100320. 468 records from (Table 3) Occurrence of dinoflagellate cyst species in ODP Hole 113-696B. 2304 records from (Table 1) Distribution of planktonic foraminifera in the upper Turonian-lower Campanian succession in ODP Hole 122-762C, Part II. 280 records from (Table 2) Numerical abundance counts of planktonic foraminifers and other biogenic constituents for ODP Hole 114-700B. 850 records from Riqueza específica y biogeografía de los corales hermatípicos de la sección sur del Golfo de California y las Islas Revillagigedo. 11779 records from Ecología y biogeografía de epífitas vasculares de Chiapas, México. 7791 records from Base de datos de las gramíneas (Poaceae) del noreste de México. 10789 records from Centre d'Estudis Avançats de Blanes. Limnological Observatory of the Pyrenees. 100026 records from Ohio State University Fish Division (OSUM). 1551 records from Abundance of benthic infauna in surface sediments from the North Sea sampled during cruise Dana00/5. 2374 records from DSMZ Collection of Filamentous Fungi and Yeasts. 80 records from Collection Copepoda - SMF. 15328 records from SOMBASE. 150169 records from UWFC Ichthyology Collection. 53482 records from Herbarium (AMNH). 5638 records from Estacion Biologica Donana - CSIC, Aves. 88 records from Teich Berlin Wuhlheide. 134 records from Birdrace-Easy_Birders-Plön. 68 records from Planktic foraminifera abundance of Hole 4-29B. 7789 records from Planktic foraminifera abundance of Hole 7-62A. 108 records from Planktic foraminifera abundance of Hole 27-263. 35 records from Planktic foraminifera abundance of Hole 67-499A. 97 records from Range table from planktonic foraminifers in ODP Hole 182-1133B. 127 records from Benthic foraminifera abundance of Hole 95-613. 3952 records from Range table from benthic foraminifers in ODP Hole 159-962D. 120 records from Phytoplankton abundance in surface water in June 1997, Chimbote, Peru. 61 records from Artenvielfalt auf der Wiese. 5286 records from Distribution of planktic foraminifers of sediment core GIK15612-2. 1073 records from Relative abundance of planktic foraminifera in sediment core RC17-69. 5 records from Analyses of the recent components of sediment core PS1012-1. 149 records from Trockenhang Greinhartsberg Edelfingen. 19 records from Landesgartenschau. 76 records from Occurrence of mammalia relicts at site Vindija. 68 records from Planktic foraminifera abundance of Hole 9-76. 16 records from Foraminifera abundance of Hole 60-453. 456 records from (Tab. 6) Distribution of benthic foraminifera in Lower Cretaceous sediments of DSDP Hole 41-370, Deep Basin West off Morocco. 63 records from Range table from benthic foraminifers in ODP Hole 172-1062B. 17 records from Range table from benthic foraminifers in ODP Hole 159-962B. 38 records from Microfossil abundance of Hole 21-206C. 528 records from Phytoplankton abundance in surface water in October 1997, Paita, Peru. 3864 records from Mammal specimen database of Kanagawa Prefectural Museum of Natural History. 900 records from Collection Agnatha fossil SMF. 89 records from Benthic macrofauna abundance in surface sediments of the east Greenland continental slope (75° N section). 3 records from Rivulus mahdiaensis, a new killifish from central Guyana (Cyprinodontiformes: Rivulidae).. 7798 records from National Invasive Species Database. 908 records from (Appendix A1) Planktonic foraminifera of ODP Hole 157-951A. 20824 records from Carabidae of the Carpathians. 873 records from Caire-Chabrand Collection. 1440 records from Museum TwentseWelle (NL) - Fossil Collection. 3709 records from Naturalis National Natural History Museum (NL) – Cnidaria and Porifera fossils. 536 records from Kieppi bird collection. 43 records from Relative abundance of planktic foraminifer Globigerinita uvula in core PS1243. 4734 records from Marine Biological Association - Volunteer sightings data held by the DASSH Data Archive Centre. 100 records from Birdrace-The_Ringers-Friesland. 12 records from Occurrence of mammalia relicts at site Kirkdale Cave. 4 records from Planktic foraminifera abundance of Hole 23-223. 159 records from Planktic foraminifera abundance of Hole 18-177A. 39 records from Planktic foraminifera abundance of Hole 28-265. 19 records from Range table from planktonic foraminifers in ODP Hole 139-858C. 5 records from Range table from planktonic foraminifers in ODP Hole 183-1136A. 944 records from (Table 2) Distribution of planktic foraminifera in early Paleogene sediments of DSDP Hole 27-259, Perth Abyssal Plain off Western Australia. 68 records from Range table from benthic foraminifers in ODP Hole 144-873B. 2 records from Dinoflagellate abundance of Hole 38-340. 1139 records from Phytoplankton abundance in surface water in September 1996, Ilo, Peru. 400 records from Phytoplankton abundance in surface water in October 1997, Callao, Peru. 52171 records from Bryophyte Collection - University of Washington Herbarium (WTU). 149 records from Apectodinium, age and percentage of endemic and bipolar dinoflagellate cysts of ODP Hole 189-1172A. 313 records from Genera of the Asian Catfish Families Sisoridae and Erethistidae (Teleostei: Siluriformes).. 2 records from Beitrage zur Kenntniss paläarctischer Myriopoden. XV. Aufsatz: Lithobiiden aus Bosnien, Herzogovina und Dalmatien. 18 records from (Table 3) Distribution of late Cretaceous nannofossils in DSDP Hole 77-538A. 1 records from Nothrus doliaris. 125 records from (Appendix I) Foraminifera abundance in DSDP Hole 7-62. 350 records from (Table 1) Distribution of Cretaceous redeposited benthic foraminifers at DSDP Hole 89-585. 1 records from Red list project inventory, bryophytes. 75791 records from SAIAB. 4276 records from Paläontologie Marburg. 14 records from Range table from planktonic foraminifers in ODP Hole 178-1101A. 1 records from Dinoflagellate abundance of Hole 38-345. 133 records from Distribution of Uvigerina proboscidea in Late Neogene sediments of DSDP Hole 22-214 in the northern Indian Ocean (Table 1). 897 records from Collection Ostracoda SMF. 6668 records from Algae (NSMK-AG). 337 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Falconidae. 1794 records from Herbarium BSG Lichenes. 2 records from Ireneopone gibber (Hym., Formicidae), a new genus and species of myrmicine ant from Mauritius.. 1851 records from (Figure 2) Foraminifera in lower to middle Albian sediments of DSDP Hole 80-549. 236754 records from Countryside Council for Wales - Welsh Invertebrate Database (WID). 3137 records from Herbarium - Las Cruces Biological Station. 1053 records from (Supplementary Table 1) Species abundance of benthic foraminifera (size fraction 150-500 µm) in sediment core GeoB11185-1. 1168 records from (Table 5) Benthic foraminifera in Pliocene sediments of DSDP Hole 90-588. 650 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Anatidae. 74 records from (Table 3) Abundance of benthic foraminifera and ostracoda in bottom sediments from the Ashadze-1 Hydrothermal Field. 55839 records from Stuart M. Fullerton Collection of Arthropods (UCFC), University of Central Florida. 6 records from Echinodermata ZMK. 19 records from (Table S1) Calcareous nannoplankton morphometric analyses performed of Cismon sediment core samples. 6211 records from NMMNH Mammal. 4 records from Note on some antlions from Mozambique (Neuroptera: Myrmeleontidae). 28 records from Hainbachtal bei Oelsnitz / V.. 32 records from Nationalpark Harz Juniorranger. 231 records from Phytoplankton abundance in surface water in October 1997, Pisco, Peru. 132 records from tab 2. 926 records from Greater Manchester Ecology Unit - Distribution of Species of Conservation Interest in Greater Manchester. 301 records from (Appendix 4, Table 4) Relative abundances of benthic foraminifera in Late Quaternary sediments of core RC09-150 in the southeast Indian Ocean. 2 records from Abundance of benthos infauna at station GIK23042-2. 5 records from Calculated abundance and biomass of Ophiocten gracilis at different stations on Kolbeinsey Ridge. 5 records from (Table 1) Test sizes of Morozovelloides crassatus from ODP Site 171-1052. 1428 records from Inventaire National du Patrimoine Naturel : Inventaire du Parc national du Mercantour. 12 records from (Table 1) Abundance and biomass of diatom algae, dinofiagellates, green algae, and flagellates and their percentages in total phytoplankton abundance and biomass in the Obskaya Guba and adjacent Kara Sea in the latest September 2007. 178 records from RSPB - Corn bunting surveys on the Western Isles. 16102 records from EcoRecord - Diptera Records held by EcoRecord for the Birmingham and the Black Country area collated prior to March 2013. 1 records from Zetes flavipes. 1 records from Oribates fusifer. 3 records from Seodaemun Museum of Natural History Mammal. 192 records from (Table 2) Relative abundance of selceted benthic foraminifera taxa of DSDP Hole 93-605. 9024 records from Cumbria Biodiversity Data Centre - Norman and Florence Hammond records. Seawatch and coastal survey records.. 2419291 records from British Bryological Society - Bryophyte data for Great Britain from the British Bryological Society held by BRC. 106941 records from Countryside Council for Wales - Welsh Peatland Invertebrate Survey (WPIS). 17 records from MVZ Herp Observations (Arctos). 3 records from (Table 2) Mercury concentration in hair of Northwest Greenland polar bears (Ursus maritimus). 23052 records from RSPB - Swift Inventory of Low-Level Screaming Parties in the UK, 2009 (RSPB and Swift Conservation Groups). 461 records from Guadeloupe_Bananier. 238 records from (Table 14) Calcareous nannofossil occurrences in ODP Hole 130-806B. 17532 records from BioFresh Pond Data. 1 records from Arthropoden aus südostalpinen Höhlen.. 65 records from (Table 4) Pleistocene nannofossil range chart for ODP Hole 134-827A. 1180 records from Nottinghamshire Biological and Geological Records Centre - Nottinghamshire Water Vole Records. 68 records from Alien Species in Poland - Plants. 1207 records from Calcareous nanofossils in late Pliocene sediments of ODP Site 162-982. 58475 records from Oregon State University Herpetological Collection. 3 records from Revision der Ceratozetidae, 3. Ceratozetes laticuspidatus n. sp. (Arach., Acari, Oribatei). 330041 records from University of British Columbia Herbarium (UBC) - Vascular Plant Collection. 231 records from (Appendix A) Benthic foraminiferal census data for extinction, uniserial survivor and high-flux, low-oxygen tolerant groups for ODP Hole 107-654A. 8332 records from Joint Nature Conservation Committee - Scotland Otter Survey Database. 559 records from (Table 2) Planktonic foraminifera community at DSDP Hole 94-610. 2212 records from RIVM (NL) - Earthworm Observations in Soil Samples. 3643835 records from Florabank1 - A grid-based database on vascular plant distribution in the northern part of Belgium (Flanders and the Brussels Capital region). 8 records from (Table 2) Monthly statistics of king penguin (Aptenodytes patagonicus) colony arrivals, Possession Island. 1 records from Oppiella signata, eine neue Art der Familie Oppiidae aus dem Osterzgebirge (Acari, Oribatei). 882456 records from South Australia Fauna Observations. 7551636 records from Birds Australia, Birdata. 589 records from (Appendix B) Benthic foraminifera extinction group polpulation of ODP Hole 184-1146A. 64 records from Pilzlehrwald. 162 records from (Appendix G) Benthic foraminifera accumulation rates of ODP Site 167-10121. 45748 records from 2011 Breeding Bird Survey of Taiwan. 3367 records from (Figure 4) Distribution of dinoflagellate cysts in the Albian/Cenomanian of DSDP Hole 79-547A. 1 records from Cepheus latus. 34502 records from Merseyside BioBank - North Merseyside Birds (verified). 355 records from Culture Collection of Cryophilic Algae. 48 records from (Table T2) Biostratigraphy of calcareous nannofossil taxa in ODP Hole 183-1136A. 90 records from (Table 2) Occurrence of larger benthic foraminifers in ODP Hole 133-823C. 9 records from A new species of Margaromantis Piza, 1982 (Insecta: Mantodea) from Brazil. 1547 records from West Wales Biodiversity Information Centre - Sea Trust Stena Europe Survey of Cetaceans in the St Georgeâs Channel, April 2004- April 2011. 29691 records from University of Amsterdam (NL) – Benthos monitoring of the North Sea research database. 334 records from (Appendix 2) Stratigraphic distribution of key and potential stratigraphic calcareous nannofossil markers in the upper Campanian-Maastrichtian of ODP Hole 122-762C. 333 records from Distribution of calcareous foraminifers in sediment core Well 6407/7-2. 120 records from Assemblage of living benthic foraminifera in sediment core GeoB3604-1. 129 records from Assemblage of living benthic foraminifera in sediment core GeoB3705-2. 131 records from Total foraminifera counts from multinet M31/2_MSN887. 12 records from Plasm bearing foraminifera counts from multinet M31/2_MSN895. 180 records from Plasm bearing foraminifera counts from multinet SO119_MSN1281. 142 records from Total foraminifera counts of multinet M21/2_MSN649. 155892 records from Lund Museum of Zoology - Insect collections (MZLU). 1 records from Dolistenus menozzii n. sp. della famiglia Platydesmidae (Miriapodi Colobognati); e altri miriapodi della Calabria. 175 records from (Table 6) Benthic foraminifera genera assemblage at DSDP Section 80-548A-16-3. 220 records from (Figure 1b) Distribution of planktonic foraminifera in bottom sediments of Core Vy20-3182. 1641 records from NCSM PaleoBotany Collection. 1415 records from Plant observations from Białowieża National Park. 4852611 records from Bird Ringing Centre in Sweden (NRM). 8629 records from National Taiwan University. 2432 records from RSPB - Black Grouse Recovery Project Annual Survey in Argyll & Bute 2002-2009 (RSPB/SNH/FCS/Scottish Power). 5450 records from Collection paléontologique du Museum d'histoire naturelle de la ville de Bourges (BOUM). 117 records from Wassermann. 58 records from Schulhof der Astrid-Lindgren-Schule und Umgebung (Elmshorn). 85 records from Ober-Olmer Wald. 16 records from Assemblage of living benthic foraminifera in sediment core SO129_MC-09, 63-125 µm fraction. 998 records from (Appendix 6) Benthic foraminifera at termination II in sediment core GIK23414-9 in the Norwegian Sea. 172 records from Benthic foraminiferal number, diversity, and species abundance of size fraction 63-125µm across sapropel S5 in core M40/4_67SL from the lower bathyal of the western Levantine Basin. 112 records from Abundance of dead benthic foraminifera in sediment core CD86_06_BC5. 75 records from Faunal assemblage of sediment core TR149-32. 442 records from Distribution of planktic foraminifera of sediment trap NB7. 238 records from Total foraminifera counts from multinet M31/3_MSN913. 19 records from Plasm bearing foraminifera counts from multinet M31/2_MSN888. 60 records from Total foraminifera counts from M35/1_MSN1063. 75 records from Foraminifera species abundances from tow TT007_8-MOC15. 10 records from schlittschuhweiher. 949 records from Percentage analysis of dinoflagellate cyst taxa groups from surface sediment samples of the eastern Indian Ocean. 28 records from Hecke - Klassen 2 a und 2 b VS Tussenhausen. 303 records from Garten J. Scherrer (Lachen-Speyerdorf). 87 records from Hartholzaue an der Dreisam (Freiburg/March-Hugstetten). 144 records from BIRDRACE Die Mohrenlerchen. 61 records from Assemblage of living benthic foraminifera in sediment profile GeoB4913-4. 346 records from Benthic foraminifera counts of sediment core GIK23342-6. 233 records from Total foraminifera counts from M35/1_MSN1044. 48 records from Content of coarse fraction and G. menardii in sediment corev V25-44. 144 records from Abundance of planktic foraminifera at CTD station M39/4_381CTD-34. 8 records from Microzooplankton abundance and biomass at station TT045_29-1. 1 records from Microzooplankton abundance and biomass at station TT050_4-7. 2 records from Nano and microzooplankton abundance and biomass at station NBP97-01-13-4. 12 records from Phytoplankton abundance at station Casma_2003-04-14_1, Casma, Peru. 174 records from (Table 5) Absolute abundances of planktonic foraminifera in Maastrichtian to upper Thanetian sediments of DSDP Hole 43-384. 15 records from (Table 2) Abundance of benthic foraminifers of sediment core PS2177-3. 6768 records from MfN - Fossil vertebrates III. 16 records from Smear slide analysis on sediment core GeoB4223-2. 66 records from Nannofossil abundance of Hole 47-398D. 19 records from Range table from ostracoda in ODP Hole 143-865A. 12722 records from Colección Ictiológica del Instituto Alexander von Humboldt. 704 records from Planktic foraminifera counts of sediment core V18-207. 2 records from Atlaszeder in Oma´s Garten. 2212 records from Collection Polychaeta - ZSRO. 18 records from Landschaftsschutzgebiet Buchhorst2. 16 records from Assemblage of living benthic foraminifera in sediment core SO129_MC-14, >125 µm fraction. 62 records from Abundance of living benthic foraminifera in sediment core CD86_10_BC4. 121 records from Total foraminifera counts from multinet M31/2_MSN893. 147 records from Total foraminifera counts of multinet M10/2_MSN295. 1 records from Microzooplankton abundance and biomass at station TT050_17-5. 1 records from Microplankton counts and carbon biomass at station TT007_12-CTD145. 6 records from Microplankton counts and carbon biomass at station TT008_5-CTD42. 119 records from Phytoplankton abundance at station CD46_0705C#4. 5 records from Distribution of meiobenthos in sediment core M19_201-2 of the northeastern Atlantic (Table 1). 119 records from Distribution of planktonic foraminifera of sediment core SH1972_16. 8 records from Abundance of radiolaria at station LV28-29-1. 1000 records from Plant specimens of Natural History Museum, Kishiwada City. 32077 records from MfN - Fossil invertebrates Ia. 3 records from Nannofossil abundance of Hole 7-64. 2 records from Nannofossil abundance of Hole 8-71. 9 records from Diatom abundance measured on water bottle samples at station PS58/045-2. 8 records from Phytoplankton abundance measured on water bottle samples at station PS65/522-1. 14 records from Benthic macrofauna abundance of sediment core 12930-028. 1824 records from (Table 6) Distribution of live benthic foraminifera in deep-sea surface sediments of the Scotia Sea, part 2. 921 records from Importancia de las lombrices de tierra (Oligochaeta) en el monitoreo de áreas prioritarias de conservación del centro, este y sureste de México. 2 records from Akita Prefectural Museum＋Specimens of Class Pycnogonida of Akita Prefectural Museum. 1872 records from Abundance of planktonic foraminifera in surface sediments of the South Atlantic. 31 records from Content of coarse fraction and G. menardii in sediment corev V25-63. 24 records from Abundance, biovolume and biomass of heterotrophic dinoflagellates at station TT012_5-CTD20. 15 records from Phytoplankton abundance at station Sechin_2003-12-10_2, Casma, Peru. 233 records from Phytoplankton abundance and species composition in the Tyrrhenian Sea in November 1981. 174 records from (Table 5) Relative abundances of planktonic foraminifera in Maastrichtian to upper Thanetian sediments of DSDP Hole 43-384. 20 records from Abundance of radiolaria at station LV28-4-1. 9 records from Abundance of radiolaria at station UT99-24-1. 134 records from Coleoptera identified from the Bellot Street site, Greenwich, London. 12 records from Cyanobacteria, phototrophic and heterotrophic pico-nanoplankton at station TT007_6-CTD67. 1 records from Ueber Chilopoden aus westbalkanischen Hoehlen. 14 records from Nannofossil abundance of Hole 39-353. 40 records from Nannofossil abundance of Hole 14-142. 19 records from Nannofossil abundance of Hole 24-233. 8 records from Phytoplankton abundance measured on water bottle samples at station PS65/546-2. 2779 records from Museu Paraense Emílio Goeldi - Herbarium Fanerógama Collection. 18 records from Benthic macrofauna abundance of sediment core 13201-002. 2343 records from (Appendix A) Planktic foraminifer abundance of ODP Hole 117-723B. 26896 records from Vascular plants database of Atugi City Museum. 3362 records from Coimbra Collection of Algae. 343 records from Collection Cnidaria - ZMB. 113 records from Survey of benthic and other marine invertebrates of Prydz Bay, 1990/91 Voyage 6. 632 records from (Table 2) Relative abundances of benthic foraminifera in ODP Hole 105-645B. 1104 records from (Table 11) Distribution of planktonic foraminifers in ODP Hole 108-657A. 68 records from Microzooplankton (larger protists and small copepods) abundance measured on concentrated water bottle samples at station PS65/593-9. 15 records from Abundance of microzooplankton measured on water bottle samples during METEOR cruise M17/1. 11 records from Microzooplankton abundance and biomass at station TT045_17-2. 278570 records from Biological Records Centre - Database for the Atlas of Freshwater Fishes. 88 records from Microzooplankton abundance measured on water bottle samples at station PS58/046-3. 4352 records from (Fig. 3) Stratigraphic ranges of Oligocene planktonic foraminifera and identified biozones in DSDP Hole 77-538A. 2392 records from Benthos counted on dredged samples during Valdivia cruise VA44. 23 records from Coccolith counts of multinet SO119_MSN1303. 14 records from Nannofossil abundance of Hole 14-140. 9 records from Nannofossil abundance of Hole 66-490. 11 records from Diatom abundance measured on water bottle samples at station PS58/061-3. 51 records from Nannofossil abundance in sediment core PS1293-4. 287 records from (Table 3) Distribution of planktonic foraminifera in the smaller size fraction of ODP Hole 120-749B. 65 records from Cuxhaven Schlosspark, Klasse 5e- Amandus-Abendroth-Gymnasium. 184 records from (Table 10) Occurrence of benthic foraminifera in ODP Hole 112-688A. 9038 records from Naturhistorisches Museum Mainz, Zoological Collection. 742 records from Composición y estructura de la ornitofauna de la reserva de la biósfera Pantanos de Centla. 3087 records from Herpetile collection, Natural History Museum, University of Oslo. 249 records from (Table 1) Relative abundance of selected benthic foraminifera in ODP Hole 104-644A. 1891 records from (Figure 4) Range charts of selected dinoflagellate cysts in ODP Hole 122-763B. 598 records from (Table 2) Eocene-Oligocene benthic foraminifers abundance in ODP Hole 124-767C. 3666 records from (Table 5) Stratigraphic ranges of selected Oligocene to earliest Miocene planktonic foraminifers in ODP Hole 115-709A. 26 records from (Table 4) Mean values of the chemical data from the ash layers from ODP Legs 113 and 114. 2 records from Fig. 7. Pollen record of profile SAO4 (Analyst: G.N. Shilova). 51438 records from Dinoflagelados y Diatomeas del Pacífico tropical mexicano. 5804 records from Propuesta para rescatar y conservar la paleobiota de la Cantera Tlayúa, en Tepexí de Rodríguez, Puebla: Fase II. 279 records from Herbarium of Lars Levi Laestadius. 7602 records from Finnish Entomological Database: Trichoptera. 1 records from (Table 5) Composition of stomach boluses of flounders in the West Bay of the Furugelm Island (Sea of Japan) in summer 1991. 4580 records from BCCM/IHEM - Biomedical Fungi and Yeasts Collection. 30380 records from Universidad de Oviedo. Departamento de Biología de Organismos y Sistemas: FCO. 53 records from Fonoteca Zoológica, Museo Nacional de Ciencias Naturales, Madrid: FZ_REPTILIA. 573 records from Macrobenthic species of the Eastern South Pacific (OBIS South America, SOUTH PACIFIC NODE). 7 records from Analyses of the recent components in the sand fraction of sediment core PS1220-3. 47 records from Pollen analysis of sediment core T89-16-PC. 906 records from Biodiversidad acuática del río Amacuzac, Morelos, México. Fitoplancton. 870 records from Contribución al conocimiento de la flora útil de la selva Lacandona. 2074 records from Patrones de diversidad florística y faunística del área focal Ixcan, selva Lacandona, Chiapas. Aves. 1001 records from Ictiofauna insular del medio y bajo Golfo de California. 1057 records from Hongos ectomicorrizógenos y myxomycetes asociados con Picea chihuahuana en la Sierra Tarahumara. 5186 records from Distribución conocida y potencial de 48 especies de hongos silvestres comestibles en la región central del país. 4000 records from Mollusk Collection of Yokosuka City Museum. 8 records from Description of lithologic section units of IODP Hole 325-M0049B. 563 records from Antarctic Marine Protists species checklist. 13865 records from Departamento de Biolog. Veg. II, Facultad de Farmacia, Universidad Complutense, Madrid: MAF-Lich. 10336 records from The Deepwater Program: Northern Gulf of Mexico Continental Slope Habitat and Benthic Ecology - DgoMB: Macrofauna. 210 records from Donald F. Hooper Butterfly collection, Canada. 163562 records from Bird specimens. 25333 records from Western Palearctic migratory birds in continental Africa. 21593 records from CNCR/Colección Nacional de Crustaceos. 11702 records from The Erysiphales Collection at the Botanische Staatssammlung München. 556 records from RMT Trawl catch from 1985/86 V1 ADBEX III voyage. 70213 records from Coleção de Abelhas do Departamento de Biologia - FFCLRP/USP. 15647 records from Universidad Autónoma de Madrid, Madrid; Lepidópteros. 173 records from Sediment components of core SO82-2. 248 records from Faunal composition of sediment core MD01-2416. 1177 records from Phytoplankton abundance during Mikhail Lomonosov cruise ML47. 6557 records from (Table 5) Distribution of Neogene planktonic foraminifers in sediments of ODP Hole 115-707A. 7910 records from Distribution of 15 major fish species in the North Sea between 1959 and 1979. 70 records from Korean Aquatic Vascular Plants. 88 records from P. W. Lund collection in the National History Museum of Denmark, Copenhagen. 122 records from Kelp rafts in the Southern Ocean (Australian Antarctic Data Centre). 834 records from Relative abundance of planktic foraminifera in the 120 kyr time slice reconstruction of sediment core A180-073. 306 records from Sediment components and coccolith of core Core SO82-Sediment components and coccolith of core SO82-5. 129 records from Occurrence of mammalia relicts at site Burghöhle Dietfurt. 23 records from Occurrence of mammalia relicts at site Ochoz Cave. 25 records from Foraminifera abundance of Hole 55-430A. 18918 records from (Table 1) Distribution of benthic and planktonic foraminifers at DSDP Hole 28-270. 124 records from Range table from benthic foraminifers in ODP Hole 172-1062A. 71 records from Range table from benthic foraminifers in ODP Hole 171-1052A. 7 records from Oberservation of birds at station PS14/148 along 49° West. 64 records from VFD-RP, Taunus: Bergweide Dehe. 2075 records from Fauna y flora asociada a 18 humedales del valle geográfico del río Cauca. 251 records from (Supplement 3) Dinoflagellate cyst count data by species of the three transects OMZ (GeoB 12312, 12321, 12331), below-OMZ-seep (GeoB 12326), and OMZ-seep (GeoB 12328). 29 records from Visual Plants (144.41.33.158) - Plants from the Kakamega Forest, Kenya; Baerbel Bleher. 137 records from Zooplankton biodiversity along the central coast in the Brazilian EEZ (OBIS South America, BRAZIL) (OBIS South America, BRAZIL). 177 records from (Fig. 2) Abundance of Neogloboquadrina pachyderma sinistral in sediment core MD95-2039. 742 records from (Appendix A) Relative abundances of smaller size planktonic foraminifera in latest Maastrichtian sediments of DSDP Hole 74-525A from Walvis Ridge, South Atlantic. 298 records from Stausee (Oberdigisheim/Meßstetten). 147 records from Luch Niederlehme, Schüler der Klasse 7. 272 records from Wald am Schloss Wittgenstein Bad Laasphe. 282 records from Faberpark (Nürnberg/Stein). 206 records from Microplankton abundance at Station SEPT-1997-GN36199704605MSB04 in the euphotic zone of the Aegean Sea in September 1997. Part 2 - dinoflagellates. 23 records from Occurrence of mammalia relicts at site l´Abri Caminade-Est. 38 records from Planktic foraminifera abundance of Hole 23-227. 78 records from Planktic foraminifera abundance of Hole 14-144B. 4 records from Description of a new species of Labeo (Teleostei: Cyprinidae) from the lower Congo River.. 16 records from Planktic foraminifera abundance of Hole 19-184. 5100 records from (Figure 2) Planktonic foraminifera abundance in DSDP Hole 93-603C. 387 records from Planktic foraminifera abundance of Hole 63-467. 176 records from Planktic foraminifera abundance of Hole 62-463. 7 records from Range table from planktonic foraminifers in ODP Hole 175-1082A. 1075 records from (Tab. 12) Distribution of benthic foraminifera in Lower Cretaceous sediments of DSDP Hole 32-305, Shatsky Rise southeast of Japan. 468 records from Collection Diptera - SMF. 9 records from Analyses of the recent components of sediment core PS1013-1. 82953 records from Vascular Plants, Observations, Oslo (O). 87 records from Antarctic Euphausiacea occurence data from Polish FIBEX expeditions. 48 records from Deutsche Schule Budapest. 627738 records from Biological Records Centre - Moths - John Heath Lepidoptera recording scheme macro-moth data from BRC. 1 records from Occurrence of mammalia relicts at site Egtved. 4 records from Occurrence of mammalia relicts at site Seest. 5 records from Occurrence of mammalia relicts at site Prekonoska Pecina. 207 records from Foraminifera abundance of Hole 58-444. 163 records from Planktic foraminifera abundance of Hole 32-313. 1347 records from (Table 16A) Occurrences of planktonic foraminifers in DSDP Hole 90-594, samples 594-1-CC through 594-30-CC. 1908 records from (Figure 3) Distribution of planktonic foraminifers in the Cenozoic sediments of DSDP Hole 71-511. 577 records from Planktic foraminifera abundance of Hole 84-565. 2407 records from Range table from planktonic foraminifers in ODP Hole 139-857A. 529 records from Range table from planktonic foraminifers in ODP Hole 141-861C. 960 records from (Table 11) Benthic foraminifera in Pliocene sediments of DSDP Hole 90-591. 973 records from Range table from planktonic foraminifers in ODP Hole 157-954B. 25 records from Benthic foraminifera abundance of Hole 1-4. 73 records from Range table from benthic foraminifers in ODP Hole 172-1059A. 90 records from Range table from benthic foraminifers in ODP Hole 146-889B. 264 records from Phytoplankton abundance in surface water in January 1996, Callao, Peru. 5164 records from Inventaire National du Patrimoine Naturel : Programme CARTHAM: Inventaire biologique dans le cadre de Natura 2000 en Mer. 3780 records from Distribution of benthic foraminifers (dead) in surface sediments (Table 5). 698 records from Tertiary benthic foraminifera abundance of Hole 95-612. 533 records from Benthic foraminifera abundance of Hole 84-567A, Part 1. 13 records from Range table from benthic foraminifers in ODP Hole 177-1088B. 59948 records from Polish gene bank – passport data of plants accessions which are important in human life. 24 records from Range table from dinoflagellates, acritarchs and prasinophytes in ODP Hole 189-1171C. 1895 records from Table A2. Benthic foraminifera assemblage of sediment core GeoB1214-1. 15 records from Benthic foraminifera assemblages and stable isotopes of sediment core PS2458-4. 144 records from Whale Observations from the British, Australian and New Zealand Antarctic Research Expedition (BANZARE) voyages 1929-30 and 1930-31. 52 records from Abundance of epibenthic echinoderms at seafloor photography station PO196_1009. 1 records from Hoplophora longula. 196 records from Inventario de Aves en la Finca Naranjitos; Aracal, Yopal, Casanare. 324 records from Tentaculata collection of National Museum of Nature and Science. 19932 records from The Arthropoda Varia Collection at the Zoologische Staatssammlung München. 11268 records from Aphidoidea Collection. 1 records from Beitrage zur Kenntniss paläarctischer Myriopoden. XV. Aufsatz: Lithobiiden aus Bosnien, Herzogovina und Dalmatien. 1 records from Ameisen aus Nossi-Bé, Majunga, Juan de Nova (Madagaskar), den Aldabra-Inseln und Sansibar. Gesammelt von Herrn Dr. A. Voeltzkow aus Berlin.. 2 records from Neobythitoides serratus, a new bathyal genus and species from the East China Sea (Teleostei, Ophidiidae).. 63 records from Museu Paraense Emilio Goeldi - Ricinulei Collection. 6422 records from Ájtte. 9 records from Rivulus uakti sp. n. and R. amanapira sp. n. (Teleostei: Cyprinodontiformes: Rivulidae): two new species from the upper Rio Negro, Brazilian Amazon.. 4 records from Evidence for the continued presence in New Zealand of Homotrysis macleayi (Borchmann, 1909) (Coleoptera: Tenebrionidae: Alleculinae). 5202 records from (Table 1) Distribution of benthic foraminifera on sediment core PS2837. 179 records from Relative abundances of benthic foraminifera in surface sediments (Table A3). 6232 records from COMARGIS: Information System on Continental Margin Ecosystems. 3439 records from MEXU/Flora de Oaxaca. 195 records from New synonymy, new species, new keys to Neivamyrmex army ants of the United States.. 42 records from (Table 2) Abundance of Globigerinoides sacculifer and Globigerinoides ruber and oxygen and carbon stable isotopes of different planktonic foraminifers at DSDP Hole 78-543. 228 records from Herbier Flora selecta exsiccata publié par Ch. MAGNIER (BOUM). 107 records from (Figure 8) Distribution and character of selected biogenic and lithologic components at DSDP Hole 79-547A. 2 records from Two new species of Baeus (Hymenoptera: Scelionidae) from southeastern Brazil parasitoids of Anelosimus (Araneae: Theridiidae).. 701889 records from Shropshire Ecological Data Network - Shropshire Ecological Data Network Database. 9682 records from (Table 1) Stratigraphic ranges of planktonic foraminifers in ODP Hole 144-871A. 779 records from Guadeloupe_Ananas. 333 records from Phytoplankton measured on water bottle samples during THALASSA cruise PROSOPE. 584 records from Yorkshire Wildlife Trust - Yorkshire Wildlife Trust Shoresearch. 1605 records from Hare Survey of Ireland 06/07. 13631 records from Beetles (LSM). 6848 records from Ratti Master Thesis / Fraser Valley, British Columbia. 172345 records from Conchological Society of Great Britain & Ireland - Mollusc (non-marine) data for Great Britain and Ireland. 129 records from (Table 2) Planktonic foraminifer abundance in ODP Section 167-1021C-10H-2. 20 records from Heteroptera - SMNG. 44051 records from Alterra (NL) - Entomofauna inventory in peat swamps. 3592 records from Zoological Museum Amsterdam, University of Amsterdam (NL) - Invasive Insecta. 93 records from Haarbach Höfe. 586 records from Aspilota-group (Hymenoptera: Braconidae: Alysiinae) diversity in Mediterranean Natural Parks of Spain. 31747 records from Syrphids of Ireland. 6987 records from National Trust - Ickworth species data held by The National Trust.. 60 records from (Table T1) Diatom biostratigraphy of ODP Hole 183-1140A. 61 records from Fig. 7 (right) Macrofossil concentrations in core Lz1104-5. 1627 records from The Irish Squirrel Survey 2007. 1 records from Nothrus gibbus. 61602 records from Greater Manchester Ecology Unit - Higher Plant Records From Greater Manchester. 433 records from Guadeloupe_Ignames. 993 records from Rossendale Ornithologists' Club - ROC RSPB Farmland Species Survey Dataset. 5 records from Arthropoden aus südostalpinen Höhlen.. 51110 records from Inventaire National du Patrimoine Naturel : Insectes Orthoptères de France. 2 records from Postia alni Niemelä & Vampola (Basidiomycota, Polyporales) – member of the problematic Postia caesia complex – has been found for the first time in Hungary. 19127 records from Biological Records Centre - Cerambycidae Dataset. 17 records from (Table T4) Calcareous nannofossil abundance of ODP Site 189-1171 sediments. 337 records from One century of vegetation change on Isla Persa, a nunatak in the Bernina massif in the Swiss Alps. 21541 records from Herbarium of the Université Libre de Bruxelles. 164 records from John Muir Trust - Species Records for John Muir Trust Properties Nevis, Sandwood, Quinag and Schiehallion 2010.. 10234 records from Collection entomologique Barthélémy. 81 records from Artenvielfalt im Schlosspark Sayn (Sayn/Bendorf). 277 records from Naturschutzgebiet Börstig bei Hallstadt. 99 records from Streuobstwiese Stedar. 192 records from Total living benthic foraminifera at station M33/1_MC-15 (WAST), size fraction >30 µm. 30 records from Plasm bearing foraminifera counts of multinet M36/6_MSN1198. 26936 records from The Brown University Foraminiferal Data Base (BFD). 12 records from Pseudanapis hoeferi, n. sp. from Central Amazonia, Brazil (Araneae, Anapidae).. 135 records from Globigerinita spp. in sediment core MSM05/5_712-2. 3 records from New species of the spider genus Olios Walckenaer, 1837 (Araneae: Sparassidae: Sparassinae) from Laos. 168 records from RSPB - Cetti's warbler national survey in the UK and the Channel Islands in 1996 (SCARRABS). 57 records from New records of ants (Hymenoptera: Formicidae) from Iran.. 2363 records from Avifauna en un área perturbada del bosque andino en el Parque Nacional Natural Farallones de Cali, corregimiento de Pance, Valle del Cauca (Colombia). 231131 records from MVZ Mammal Collection (Arctos). 53 records from Royal Horticultural Society - Wisteria scale (Eulecanium excrescens) records acquired by the Royal Horticultural Society . 1803 records from Flora of tanzania. 3015 records from Aquatic Oligochaeta of Ireland. 69 records from Revision of the subgenus Aulacomyrma Emery of the genus Polyrhachis F. Smith, with descriptions of new species.. 178 records from Conchological Society of Great Britain & Ireland - Mollusc (non-marine): Records of Fossil Molluscs for Great Britain. 6 records from First record of Tettigettalna mariae (Quartau & Boulard 1995) (Insecta: Hemiptera: Cicadoidea) in Spain. 79 records from Balkon (Norderstedt). 136 records from Grillhütte Wettsaasen, Wiese, Hecken. 11 records from Waldgebiet Todtnau- Sonnhalde. 16 records from Naturschutzgebiet "Gellener Torfmöörte" (Landkreis Wesermarsch). 67 records from Tongrube bei Hettstedt. 85 records from Rund um den Hainbergsee. 6325 records from Colección Entomológica de la Universidad de Antioquia. 54 records from Assemblage of living benthic foraminifera in sediment core SO118_MC-52, 63-125 µm fraction. 10 records from Assemblage of living benthic foraminifera in sediment core SO118_MC-02, 30-63 µm fraction. 316 records from (Appendix 6) Benthic foraminifera at termination II in sediment core GIK23068-3 in the Norwegian Sea. 16 records from Large protozoan and small metazoan abundance measured on concentrated water bottle samples at station PS65/593-18. 228 records from Phytoplankton abundance and species composition in the Gulf of Naples and the Gulf Salerno in November 1985. 6179 records from Southern Cape herbarium. 32 records from A review of the subfamily Acaenitinae Förster, 1869 (Hymenoptera, Ichneumonidae) from Ukrainian Carpathians. 1 records from Beitrage zur Kenntniss paläarctischer Myriopoden. XV. Aufsatz: Lithobiiden aus Bosnien, Herzogovina und Dalmatien. 7693 records from NHM, Heteroptera. 27639 records from Cicadelidos (Hemiptera: Cicadellidae) de Colección Entomológica del Instituto Alexander von Humboldt. 179 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Cuculidae. 71463 records from Vascular plant herbarium, Agder naturmuseum og botaniske hage. 1080 records from (Appendix) Foraminifer abundance of a volcaniclastic interval from ODP Hole 197-1206A. 3904981 records from FlorKart - FlorenKartierung Gefaesspflanzen. 3 records from A revision of the Neotropical spider genus Ancylometes Bertkau (Araneae: Pisauridae). 252 records from RSPB - Black grouse leks in the Forest of Clunie, 2002-2010 (RSPB, SNH). 1 records from Beitrage zur Kenntniss paläarctischer Myriopoden. XV. Aufsatz: Lithobiiden aus Bosnien, Herzogovina und Dalmatien. 657 records from (Table 2) Abundance of Miocene to Pleistocene dinoflagellate cysts in ODP Site 133-823. 5605 records from Distribution of barnacles, bivalves, gastropods, and calcified worm tubes in sediment samples collected between 1995 and 2010 in the San Francisco Bay coastal system. 157292 records from Hertfordshire Natural History Society Flora Group - Hertfordshire Flora Survey Records 1987-2005. 200913 records from University of British Columbia Herbarium (UBC) - Bryophytes Collection. 57928 records from Zoological Museum Amsterdam, University of Amsterdam (NL) - Lepidoptera_Nymphalidae_Palearctic. 61468 records from Naturalis National Natural History Museum (NL) – Aves_ Passeriformes. 123 records from Birdrace-Thüringer_Becken-Sömmerda. 83 records from Birdrace-Team_Eckhard_Reinstein-Hersfeld/Rotenburg. 45 records from Georgs-Padd (Wangerooge). 22 records from Altendorfer Dorfbachhöhle / Sächsische Schweiz. 114 records from Liether Kalkgrube. 269 records from BIRDRACE Dithmarscher Deichhühner. 42 records from Feuchtwiese Grüne Mitte, Klasse 5a. 61 records from (Table 1) Sedimentology of core D11957P. 2196 records from Total fauna of benthic foraminifera of Hole 44-390A, Blake Nose Plateau, North Atlantic. 54 records from Total foraminifera counts from M35/1_MSN1057. 82 records from Total foraminifera counts of multinet FCA97C_MSN1346. 102 records from Total foraminifera counts of multinet M21/4_MSN723. 59 records from Plasm bearing foraminifera counts of multinet PO247/2_MSN1388. 202 records from Total foraminifera counts of multinet M6/7_MSN96. 373 records from Distribution of planktic foraminifera (250-500 µm) of sediment core GIK23059-3. 30 records from Planktic foraminifer Globorotalia menardii counts on sediment core GeoB5130-2. 78 records from Phytoplankton counted on two fractions of surface sediment samples from Meteor stations M35003-4 to M35010-3. 11 records from Microzooplankton abundance and biomass at station TT045_11-2. 4 records from Microzooplankton abundance and biomass at station TT050_26-17. 4 records from Microzooplankton abundance and biomass at station TT054_26-21. 19 records from Abundance and carbon biomass of phytoplankton at station TT012_5-CTD38. 18 records from Abundance, biovolume and biomass of heterotrophic dinoflagellates at station TT007_3-CTD37. 24 records from Abundance, biovolume and biomass of heterotrophic dinoflagellates at station TT012_5-CTD45. 131 records from Phytoplankton abundance at station CD47_0906C#6. 668 records from Lower Albian LArboudeysse (Niveau Paquier) range chart in percentages of nannofossils, in SE France. 864 records from Lower Albian LArboudeysse (Niveau Paquier) range chart in percentages of nannofossils, in SE France. 14 records from Occurrence of recent nannoplankton in surface sediments at M1_MULT245, Arabian Sea (Fig. 2). 87 records from Artenvielfalt des "Grünen Klassenzimmers". 781 records from Benthic foraminiferal number, diversity, and species abundance of size fraction >125µm across sapropel S6 in core M40/4_KL51 from the lower bathyal of the western Levantine Basin. 17 records from Assemblage of living benthic foraminifera in sediment core CD146_55918#7, >150 µm. 232 records from Distribution of planktic foraminifera of sediment trap OG5. 91 records from Plasm bearing foraminifera counts from multinet M32/3_MSN957. 5982 records from Biodiversity records from Ireland - general. 90 records from Plasm bearing foraminifera counts from M35/1_MSN1069. 163 records from Total foraminifera counts of multinet M6/7_MSN100. 76 records from Plasm bearing foraminifera counts of multinet PO247/2_MSN1390. 164 records from Abundance of planktic foraminifera at CTD station PS55/066. 149 records from Abundance of planktic foraminifera at CTD station PS55/078-1. 1367 records from (Appendix 1) Distribution of planktonic foraminifera in sediment of the last 70 kyr of ODP Core 161-977A from the western Mediterranean Sea. 170 records from Scottish Natural Heritage - The occurrence and distribution of Najas flexilis (Slender naiad) in Loch of Craiglush, Loch of the Lowes and Loch of Butterstone. 6 records from Microzooplankton abundance and biomass at station NBP97-03-06-8. 109 records from Phytoplankton abundance at station CD46_1305C#2. 128015 records from UMMZ Mammal Collection. 16 records from Phytoplankton abundance at station Sechin_2003-10-03_2, Casma, Peru. 14 records from Phytoplankton abundance at station Sechin_2003-12-28_1, Casma, Peru. 7 records from Abundance of nematoda in sediment profile M3/1_031 from the Iberian deep sea basin (Table 5). 388 records from Geometry of coccolith Coccolithus pelagicus in sediment core GIK23062-4. 110 records from Planktic foraminifera counts at CTD station M39/4_366CTD-22. 6 records from Sarcodine counts and carbon biomass at station TT012_5-PMOC5. 6 records from Microzooplankton abundance and biomass at station NBP97-08-07-1. 7 records from Abundance of nematoda in sediment profile M3/1_012 from the Iberian deep sea basin (Table 5). 11 records from Zoobenthos in surface sediments off Cape Lucul. 12 records from Abundance of radiolaria at station LV28-44-1. 55 records from Seeufer ehem. BUGA-Gelände. 120 records from Nannofossil abundance of Hole 47-397. 5 records from Nannofossil abundance of Hole 77-536. 7 records from Abundance of empty diatom frustules measured on water bottle samples at station PS58/090-4. 19 records from Meiofauna abundance in sediment core 12930-015. 557 records from RSPB - Corn bunting breeding distribution in Scotland (RSPB/Volunteers). 665 records from Collection Echinodermata - ZMB. 135 records from (Table 2) Distribution of silicoflagellates, actiniscidians, and ebridians in selected samples from ODP Hole 112-683A. 156 records from Base de datos y colección de distintos grupos del zooplancton de regiones marinas prioritarias de Jalisco y Colima en el Pacífico mexicano. Larvas de Medusas. 4957 records from Mamíferos de los Parques Nacionales Lagunas de Montebello y Palenque, Chiapas. 394 records from Range table from benthic foraminifers in ODP Hole 144-871C. 313 records from BIRDRACE Gätkes Erben. 7 records from Abundance of nematoda in sediment profile M3/1_035 from the Iberian deep sea basin (Table 5). 907 records from (Appendix 2-8) Distribution of planktonic foraminifera in late Neogene sediments of DSDP Site 86-577 in the western Pacific Ocean. 5644 records from (Appendix 1) Planktonic foraminifera abundances in ODP Site 181-1123. 70 records from Parkuntersuchung Weißer See. 12230 records from MfN - Fossil invertebrates IIb. 213 records from Coccoliths in sediment core PS1113-1. 12 records from Cyanobacteria, phototrophic and heterotrophic pico-nanoplankton at station TT007_1-CTD8. 12 records from Cyanobacteria, phototrophic and heterotrophic pico-nanoplankton at station TT007_5-CTD56. 11 records from Diatom abundance measured on water bottle samples at station PS58/092-3. 964 records from (Appendix B) Nannofossil abundances in DSDP Hole 90-594 from the South Chatham Rise, southeastern New Zealand. 5 records from Microplankton abundance at Station MARCH-1997-GN36199704601MSB07 in the euphotic zone of the Aegean Sea in spring 1997. Part 1 - diatoms. 4 records from Distribution of Quinqueloculina sp. in sediment core 12930-084. 44 records from Matter enrichment of the macrofauna community of MAC station 13368-008. 157 records from Benthic macrofauna abundance of subcores of sediment core 13200-073. 134 records from Planktic foraminifera counts of sediment core V19-202. 64 records from (Table 2) Distribution of calcareous nannofossils in ODP Hole 119-738C. 313 records from Colecciones Zoológicas de la Universidad de León, Colección de Insectos. 30 records from Southern Ocean oligochaete occurrence data - a literature-based compilation. 145 records from Echinoderms in surface sediments off Sylt collected during Heincke cruise HE275. 36 records from Range table from benthic foraminifers in ODP Hole 160-967E. 33 records from Coccolith counts of multinet M32/5_MSN977. 12 records from Nannofossil abundance of Hole 31-299. 13 records from Nannofossil abundance of Hole 84-570. 17 records from Nannofossil abundance of Hole 3-13. 28 records from Apectodinium, age and percentage of endemic and bipolar dinoflagellate cysts of ODP Hole 189-1171D. 13 records from Benthic macrofauna abundance of sediment core 13200-081. 2 records from Föhrenried. 43453 records from Plant (NSMK-PL). 11 records from (Table 4) Distribution of calcareous nannofossils at ODP Hole 125-785A. 478 records from Macrobenthos in surface sediments off Sylt collected during Heincke cruise HE278. 40 records from (Table 1) Ostracode distribution in ODP Hole 122-759B. 24 records from (Table 6) Distribution of calcareous nannoplankton in selected samples of ODP Hole 112-683A, Part II. 1 records from (Table 1.2.1.1) Abundance of sympagic meiofauna of sea-ice core PS69/554-2. 48 records from Pollen counts of sediment core GeoB9503-5. 10 records from A new Neoplatyura Malloch from Finland (Diptera, Keroplatidae). 678 records from Ictiofauna de los ríos Papagayo, Atoyac y Coyuca. 11408 records from Molluscs of the Natural History Museum in Gothenburg. 900 records from Manual ilustrado de las orquídeas silvestres del estado de Morelos. 14202 records from Plant specimens of Hokkaido University Museum. 280 records from BIRDRACE Alb-Donaumoos-Kompetänzteam. 96 records from BIRDRACE OAG Neuwerk. 130 records from (Table 15) Distribution of ostracode species in Core PS51/135-4. 3950 records from (Table 3) Distribution of planktonic foraminifers in ODP Hole 112-682A. 18894 records from (Table 5) Stratigraphic ranges and relative abundances of Paleogene planktonic foraminifers and other selected organisms in ODP Site 114-702. 4900 records from Computarización de la Colección Regional Durango (Mammalia). 586 records from Inventario taxonómico de los hongos conidales saprobios del parque Yumka' en Villahermosa, Tabasco. 4 records from Akita Prefectural Museum＋Specimens of Class Maxillopoda of Akita Prefectural Museum. 669 records from Abundance of large foraminifera in cores from transect HYD-01C, IODP Expedition 325. 39 records from Mineralogy of serpentine muds of ODP Leg 125 holes (Table 1). 265 records from (Table 2) Planktonic foraminiferal abundances in ODP Hole 121-758C. 17374 records from Canadian Museum of Nature Amphibian and Reptile Collection - Anura. 750 records from Museu Valencià d′Història Natural - Fundación Entomológica Torres Sala: FETS. 894 records from Mammalia - Baekdu Mountain Animal (KIDR-MM). 241 records from CNIN/Tipos Odonata. 3301 records from Mariposas (Lepidoptera: Papilionoidea) de la Colección Entomológica del Instituto Alexander von Humboldt. 2397 records from Japan Collection of Microorganisms(Fungi). 634258 records from Hawk Migration Association of North America - HawkCount. 38937 records from Insect specimens of Museum of Nature and Human Activities, Hyogo Prefecture, Japan. 2187 records from Distribution of planktonic foraminifera in surface sediments of the Mediterranean Sea. 144 records from Lustbach-Umland. 17 records from Nannofossil abundance of Hole 14-135. 578 records from (Table 3) Relative abundances of selected planktonic foraminifera of ODP Site 117-722. 676 records from (Appendix D) Stable carbon and oxygen isotope composition of Globigerinoides sacculifera of ODP Hole 121-758A. 1361 records from Collection Arachnida - SNSD. 1541 records from (Appendix B3) Calcareous nannofossils of ODP Site 208-1263. 14971 records from Herbario de la Universidad de Almeria. 3617 records from Generic Taxonomic Database System on Mysida and Nematoda. 71368 records from Marine and Coastal Management - Linefish Dataset (Second Semester of 1987) (AfrOBIS). 22700 records from Royal British Columbia Museum. 25959 records from Royal Ontario Museum: Entomology. 704 records from DSMZ Collection on Plant Cell Cultures. 16 records from A new species of chimaeroid, Hydrolagus alphus sp. nov. (Chimaeriformes: Chimaeridae) from the Galapagos Islands.. 223245 records from Planetary Biodiversity Inventory Eumycetozoan Databank. 13478 records from Herp Collection. 5346 records from Araneidae specimen database of Osaka Museum of Natural History. 66 records from Planktic foraminifera assemblage in sediment core GeoB1113-4. 12113 records from Distribution of planktic foraminifers and SST of sediment core GIK15637-1. 600 records from Bulk components, concentration and planktonic foraminifera of sediment core GeoB7112-5. 1611 records from Percentages of planktonic foraminifera species in sediment core RC13-189. 1008 records from Relative abundance of planktic foraminifera in the 120 kyr time slice reconstruction of sediment core V22-196. 939 records from Planktic foraminifera distribution of sediment core SU81-07. 55747 records from Colección de Referencia de Lepidópteros Diurnos Mexicanos de la CNIN (Lepidoptera: Papilionoidea) (IBUNAM). 310 records from Umgebung der Gesamtschule Hamburg-Winterhude. 156 records from Blumenrather Heide / Virneburg. 126 records from Regionalpark(Hattersheim). 21 records from (Table 1) Dinoflagellate species and specimen abundance in Maastrichtian sediments of the Bass River Section in the southern New Jersey. 269 records from BIRDRACE Kosmos-Racer. 2904 records from (Figure 8) Distribution of benthic foraminifers in the Pliocene-Quaternary of DSDP Hole 71-514. 67530 records from Marine and Coastal Management - Linefish Dataset (Second Semester of 1986) (AfrOBIS). 172308 records from Naturalis Biodiversity Center (NL) - Coleoptera. 1070 records from CNAN/Araneae. 2883 records from Inventory of Antarctic seabird breeding sites. 348 records from Foraminifera distribution of sediment core SDSE184. 5470 records from (Supplement 1) Relative abundance of planktic foraminifera in sediments of the last 560 kyr of ODP Hole 165-999A, Caribbean Sea. 1505 records from Relative abundance of planktonic foraminifera in Pliocene and Pleistocene sediments of DSDP Hole 32-310 from Hess Rise, Central North Pacific (Table II). 14 records from Microplankton abundance at Station SEPT-1997-GN36199704606MNB06 in the euphotic zone of the Aegean Sea in September 1997. Part 3 - coccolithophores and other groups. 129 records from Occurrence of mammalia relicts at site Koziarna Cave. 20 records from Occurrence of mammalia relicts at site le Roc de Marcamps. 118 records from Planktic foraminifera abundance of Hole 17-165A. 2240 records from Derbyshire Biological Records Centre - Hemiptera Records 1969 - 2011. 325 records from Planktic foraminifera abundance of Hole 9-83. 1 records from Hypochthonius pallidulus. 15 records from Range table from planktonic foraminifers in ODP Hole 139-858B. 209691 records from Mosses (S). 15575 records from (Appendix A) Planktonic foraminifer abundance and ranges of ODP Hole 165-999A sediments. 18 records from Range table from planktonic foraminifers in ODP Hole 175-1080A. 20 records from Range table from planktonic foraminifers in ODP Hole 180-1115A. 247 records from Occurence of foraminifera and other microfossils in sediment core CRP-2/2A (Table 1). 3015 records from Bird specimens in Gifu Prefectural Museum. 6229 records from (Table 9) Percentages of planktonic foraminiferal taxa from Site GIK17940. 884 records from Percentages of planktonic foraminifera species in sediment core EN066-10PG. 1435 records from Relative abundance of planktic foraminifera in the 120 kyr time slice reconstruction of sediment core V28-345. 362 records from (Table A.05) Foraminiferal census data of sediment core PS1243-1 during marine isotopic stage 7 (100-150 µm). 2644 records from Planktic foraminifera distribution of sediment core GIK17666-2. 22 records from Antarctic Euphausiacea occurence data from Norwegian Antarctic Research Expedition 1976-77. 2504 records from Collections data on ecology of bottom animal of the Southern ocean. 410 records from Gemeindegebiet Weikendorf (Marchfeld). 31 records from Planktic foraminifera abundance of Hole 28-264. 13 records from Planktic foraminifera abundance of Hole 20-202. 2064 records from (Table 5) Distribution of planktonic and selected benthic foraminifers from DSDP Hole 87-583D. 44 records from Planktic foraminifera abundance of Hole 51-417A. 372 records from Planktic foraminifera abundance of Hole 73-523. 201 records from Planktic foraminifera abundance of Hole 32-313. 672 records from Range table from planktonic foraminifers in ODP Hole 155-938A. 294 records from Range table from planktonic foraminifers in ODP Hole 155-945A. 159 records from Range table from planktonic foraminifers in ODP Hole 180-1109C. 395 records from Range table from planktonic foraminifers in ODP Hole 180-1118A. 2 records from Benthic foraminifera abundance of Hole 42-374. 506 records from Range table from benthic foraminifers in ODP Hole 146-889A. 368 records from (Fig. 17) Distribution of dinoflagellate cysts in Early Cretaceous sediments of ODP Hole 103-641C in the North Atlantic. 71 records from Range table from silicoflagellates, ebridians and actiniscidians in ODP Hole 151-908A. 6014 records from globec/soglobec/process/krill. 1441 records from (Table 1) Count data of organic-walled dinoflagellate cysts in surface sediment samples from the Benguela System. 94 records from Occurrence of mammalia relicts at site Krapina. 16 records from Occurrence of mammalia relicts at site la Grotte des Fees. 576 records from Planktic foraminifera abundance of Hole 23-229A. 96 records from Planktic foraminifera abundance of Hole 32-305. 774 records from Planktic foraminifera abundance of Hole 80-549A. 828 records from Planktic foraminifera abundance of Hole 24-231. 401 records from Range table from planktonic foraminifers in ODP Hole 138-852B. 5 records from Range table from planktonic foraminifers in ODP Hole 171-1049C. 285 records from (Table 4) Planktic foraminiferal abundance in Oligocene to Early Miocene sediments of ODP Hole 177-1090E on the Agulhas Ridge, South Atlantic. 7351 records from Museu de Ciències Naturals de Barcelona: MCNB-Pal. 228 records from (Tab. 8) Occurence of microfossils in Late Jurassic sediments of DSDP Hole 79-547B, Mazagan Basin west of Morocco. 258 records from Dinoflagellate abundance of Hole 81-553A. 684 records from (Table 5) Distribution of benthic foraminifera in Neogene sediments of DSDP Site 21-206 in the southwest Pacific. 71 records from tab3. 83 records from Abundance of birds on the channels of Lena Delta in the brood period. 20 records from Biological Records Centre - RISC Non-Native Species Records for Rhododendron Leafhopper. 271 records from Algae - Domestic Bacteria (KIDR-AG). 3207 records from UAFMC Herps. 6035 records from Inland Fisheries Ireland data on freshwater fish in Irish lakes. 172 records from Redescription of Gymnotus coropinae (Gymnotiformes, Gymnotidae), an often misidentified species of Neotropical electric fish, with notes on natural history and electric signals.. 2379 records from Lichens from Russian Fennoscandia. 103 records from (Table 2) Distribution of living benthic foraminifera in surface sediment of the Elbe estuary. 2398 records from Fleas (Siphonaptera) of Ireland. 2443 records from Distribution of benthic foraminifera of sediment core PS1388-3. 246 records from Berkel. 73043 records from North Carolina State Museum of Natural Sciences Fishes Collection. 169 records from Whale log - observations from ANARE voyages. 91451 records from Collection Mammalia SMF. 68 records from Collection Tentakulita fossil SMF. 1 records from Cheiloneurus flaccus (Walker, 1847) (Hymenoptera: Encyrtidae), new to New Zealand. 99 records from Calcareous dinoflagellate cysts of multicorer M51/3_569-3, grain fraction < 20µm. 21900 records from Jena Microbial Resource Collection (JMRC) at Leibniz Institute for Natural Product Research and Infection Biology e.V. Hans-Knöll-Institute (HKI) and Friedrich Schiller University Jena. 1603 records from (Table 1) Relative abundance of planktonic foraminifers in ODP Hole 164-997A sediments. 140 records from Plant Living in Water (KIDR-PL). 226 records from Molecular and morphological characterisation of new species in the trapdoor spider genus Aname (Araneae: Mygalomorphae: Nemesiidae) from the Pilbara bioregion of Western Australia. 662 records from RSPB - Snipe survey of key sites in Britain in 2006 (RSPB and Natural England). 205 records from Fortalecimiento de los procesos de recuperación natural y cultural en la Sierra Nevada de Santa Marta. 29 records from Revision of the genus Euthalenessa Darboux (Polychaeta: Sigalionidae). 84 records from (Table 1) Occurrence of larger benthic foraminifers in ODP Hole 133-817D. 569 records from (Appendix D) Benthic foraminifera extinction group species in DSDP Hole 94-608. 259408 records from MSB Mammal Collection (Arctos). 8328 records from Zoological Museum Amsterdam, University of Amsterdam (NL) - Diptera_Tipulidae_Palearctic. 707 records from Merseyside BioBank - Merseyside BioBank Active Naturalists (verified). 656 records from Absolute abundance of dead benthic foraminifera of sediment core M5/2_107MC. 2079 records from (Table 1) Occurrence and frequency of benthic foraminifera in Paleocene samples of DSDP Hole 93-605. 740 records from (Table T15) Planktonic foraminifera stratigraphy of ODP Hole 198-1211A, Zones P6b-P8. 104 records from Kamptozoa collection of National Museum of Nature and Science. 18970 records from Cowan Tetrapod Collection - Birds. 49 records from A catalogue of the ants of Paraguay (Hymenoptera: Formicidae).. 21912 records from Herbarium specimens of Herbiers Universitaires de Clermont-Ferrand (CLF). 1 records from Diagnosies provisoires de quelques espèces nouvelles de fourmis de Madagascar, récoltées par M. Grandidier.. 54 records from Herbier de l'Ecole Normale de Bourges (BOUM). 25128 records from Royal Museum of Central Africa - Albertian Rift Butterflies (ENBI wp13). 1320 records from (Table T14) Planktonic foraminifera stratigraphy of ODP Hole 198-1211A, Zones P4a-P6a. 1284 records from Collection of Heteroptera. 42659 records from Zoological Museum Amsterdam, University of Amsterdam (NL) - Aves. 8007 records from Segunda caracterización biológica de aves del proyecto "Incorporación de la Biodiversidad en el sector cafetero en Colombia". 292 records from Gymnotus ucamara: a new species of Neotropical electric fish from the Peruvian Amazon (Ostariophysi: Gymnotidae), with notes on ecology and electric organ discharges.. 412 records from Fossil occurrence from planktonic foraminiferas from IODP Hole 315-C0001E. 96 records from (Table T4) Biogenic and mineral composition of sediments cored in Hamburg-Langenhorn. 948 records from Field Study Group of the Dutch Mammal Society (NL) - 2008 - Mammal Survey Muntii Padurea Craiului - Apuseni mountains, Romania. 33 records from (Table 6) Distribution and abundance of calcareous-nannoplankton species in the Cretaceous sediments of DSDP Hole 62-466. 27 records from Laubwald Dreiländereck (Aachen/Vaals[NL]). 540 records from (Appendix 3) Abundances of benthic forminifera in DSDP Hole 74-525A. 979 records from Herbier_CNSF. 1 records from Nothrus furcatus. 680 records from (Table 1) Distribution of larger benthic and planktonic foraminifers in ODP Hole 135-841B. 6 records from A new species of Stasimopus from the Eastern Cape Province of South Africa (Araneae, Mygalomorphae, Ctenizidae), with notes on its natural history. 562 records from A preliminary checklist of the ants (Hymenoptera: Formicidae) of Iran.. 189 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Podicipedidae. 113 records from Naturalis Biodiversity Center (NL) - Crustacea. 140 records from Three new percid fishes (Percidae: Percina) from the Mobile Basin drainage of Alabama, Georgia, and Tennessee.. 204 records from (Table 8) Sample mass, sand fraction and relative abundances of planktonic foraminifera in ODP Holes 127-794A and 127-197B. 5 records from (Figure 8) Relative abundance of nannoliths at DSDP Hole 62-464. 39035 records from Merseyside BioBank - North Merseyside Birds (unverified). 58 records from A revision the Australian species of the ant genus Myrmecina (Hymenoptera: Formicidae).. 28 records from Colección de Cocodrilos y Caimanes Museo de La Salle Bogotá (MLS). 14533 records from Tasmanian Museum and Art Gallery provider for OZCAM. 7 records from An unusual new species of Micraspis Chevrolat (Coleoptera: Coccinellidae) from northeastern India. 2 records from Filling in the gap: two new records and an updated distribution map for the Gulf Sand gecko Pseudoceramodactylus khobarensis Haas, 1957. 1 records from Oribates mollicomus. 22 records from Heilpflanzen im Hainbachtal. 63 records from Sternwiese Mülheim-Broich. 27 records from Bäche im Mooswald (Vörstetten). 38 records from Aktionstag "Artenvielfalt der Feuchtwiesen bei Daubringen". 38 records from Abundance of dead benthic foraminifera in sediment core CD86_07_BC4. 9589 records from (Appendix) Distribution of planktonic foraminifers at DSDP Hole 72-516F, Coniacian-Santonian to upper Maestrichtian. 2252 records from Nijmegen Natural History Museum (NL) – Herbarium. 2387 records from The French Collection of Medicago truncatula. 10 records from Two new species of eelpouts (Teleostei, Zoarcidae) of the genus Seleniolycus from the Ross Dependency, Antarctica.. 55 records from A taxonomic revision of the Pheidole roosevelti-group (Hymenoptera: Formicidae) in Fiji.. 2 records from Studies on the ant fauna of Melanesia V. The tribe Odontomachini.. 1139 records from SWECO. 1 records from Copepod order counts from various box corer samples of cold-water coral substrates in the Porcupine seabight. 7677 records from Macroinvertebrate abundance in river biotopes across England and Wales. 24 records from From Corsica to Britain: new outdoor records of Ocnerodrilidae (Annelida: Clitellata) in western Europe. 30 records from Phytoplankton abundance in the wadden sea off List, Sylt, North Sea in 2000. 609 records from Countryside Council for Wales - Bat Roosts Database- South Wales . 4400 records from USAC Mammals Collection. 97 records from (Table 1) Distribution of calcareous nannofossils in ODP Hole 167-1017E sediments. 1238 records from Insect Collection (CeStuBio). 1 records from Pollen analysis of sediment profile BIB00 from Biber See. 13389 records from Herbario Nacional de Plantas Celulares - Museo Argentino de Ciencias Naturales 'Bernardino Rivadavia'. 11 records from (Figure 4) Distribution of late Paleocene calcareous nannofossils in ODP Hole 132-810C. 4 records from (Figure 10) Relative abundance of nannoliths at DSDP Hole 62-466. 156 records from Botanischer Garten (Saarbrücken). 391 records from Wildes Bremer Leben im Park. 335 records from Meiofaunal abundance in sediments obtained during RRS Discovery cruise D297. 11251 records from Herbarium areqvipense (HUSA). 97660 records from CAS Ornithology (ORN). 2789 records from Caracterización de flora, edafofauna epígea, anfibios y aves del complejo de Páramos de Sotará, Cauca. 25 records from Countryside Council for Wales - Freshwater Gwyniad Survey Data. 129 records from Mammalia (KNAM-MM). 21 records from Riedkanal Bötzingen. 95 records from BIRDRACE accipiter hardcore birding. 102 records from http://www.geo-artenvielfalt.de (www.geo-artenvielfalt.de) - BIRDRACE *Bkassine*. 91 records from Plasm bearing foraminifera counts from multinet SO119_MSN1295. 157 records from Total foraminifera counts from M35/1_MSN1069. 50 records from Total foraminifera counts of multinet M21/5_MSN743. 1 records from Microplankton counts and carbon biomass at station TT008_6-CTD64. 4 records from Nano and microzooplankton abundance and biomass at station NBP97-01-19-2. 5 records from A new species of Nanochromis (Teleostei: Cichlidae) from Lake Mai Ndombe, central Congo Basin, Democratic Republic of Congo.. 31 records from Meiofauna abundances at the Arctic Håkon Mosby Mud Volcano (HMMV) of sediment core PS64/363-1a. 267 records from Phytoplankton abundance and species composition in the North Balearic Sea in March 2003. 44 records from (Table F3) Occurrence of some well known benthonic foraminiferal species in samples from DSDP Site 6-49. 1 records from Zetes dorsatus. 40 records from Coccolith counts of multinet M32/5_MSN990. 33 records from Coccolith counts of multinet SO119_MSN1272. 2 records from Nannofossil abundance of Hole 3-19. 7 records from Nannofossil abundance of Hole 9-82. 761 records from Abundance of benthic infauna in surface sediments from the North Sea sampled during Walther Herwig cruise WH220. 14 records from Assemblage of living benthic foraminifera in sediment core CD146_55907#1, 63-150 µm. 11 records from Plasm bearing foraminifera counts from multinet M31/2_MSN896. 141 records from Plasm bearing foraminifera counts from multinet SO119_MSN1282. 70 records from Plasm bearing foraminifera counts from multinet SO119_MSN1283. 210 records from RSPB - Black grouse lek survey in the Scottish Borders, 2010 (Southern Upland Partnership). 132 records from Total foraminifera counts of multinet M10/2_MSN315. 142 records from Total foraminifera counts of multinet M21/3_MSN675. 102 records from Plasm bearing foraminifera counts of multinet M42/3_MSN1360. 132 records from Abundance of planktic foraminifera at CTD station PS55/080-1. 74 records from Dinoflagellate cysts of mooring MST-8 (station 905) with cell content. 10 records from Microzooplankton abundance and biomass at station TT043_15-1. 2 records from Microzooplankton abundance and biomass at station TT050_15-3. 5 records from Microzooplankton abundance and biomass at station TT050_7-9. 4 records from Microzooplankton abundance and biomass at station TT054_24-21. 14 records from Abundance and carbon biomass of phytoplankton at station TT007_3-CTD30. 24 records from Abundance, biovolume and biomass of heterotrophic dinoflagellates at station TT008_5-CTD18. 1 records from Microplankton counts and carbon biomass at station TT011_4-CTD46. 1 records from Microplankton counts and carbon biomass at station TT011_8-CTD96. 510 records from Alterra (NL) - Microarthropods inventory in a range of forests. 10 records from Phytoplankton abundance at station Sechin_2003-07-15_2, Casma, Peru. 22 records from Microzooplankton abundance measured on water bottle samples at station PS65/546-2. 670 records from Pilstingermoos. 78 records from Total foraminifera counts of multinet M12/3_MSN541. 68 records from Total foraminifera counts of multinet M21/4_MSN701. 62 records from Plasm bearing foraminifera counts of multinet M21/5_MSN728. 233 records from Distribution of planktic foraminifera (125-250 µm) of sediment core GIK23059-3. 111 records from Planktic foraminifera counts at CTD station PS55/037. 331 records from Size of planktic foraminifera at CTD station PS55/082-1. 13 records from Phytoplankton abundance at station Sechin_2003-08-27_1, Casma, Peru. 31 records from Sandloch - Höhle. 142 records from MfN - Fossil vertebrates I. 48 records from Nanoplankton abundance at station GeoB2005-5. 24 records from Nannofossil abundance of Hole 8-72. 26 records from Nannofossil abundance of Hole 37-332A. 31 records from Bayerische Donau - Tapfheim. 1 records from On the Chilopoda from Turkey. 108 records from Benthic foraminifera abundance in ODP Leg 155 holes. 204 records from Dinoflagellates and pollen of the Brito-Arctic Igneous Province flora, ODP Hole 104-642E. 486 records from (Table 5) Relative abundance of selected benthic foraminifera in ODP Hole 104-643A. 12613 records from Base de datos del Herbario de la Unidad Académica de Agronomía de la Universidad Autónoma de Zacatecas. 5080 records from Riqueza específica, distribución y abundancia de aves terrestres y marinas en Isla San José, Golfo de California, Baja California Sur, México. 3538 records from (Table 4) Paleocene to Eocene planktonic foraminifera of DSDP Hole 29-277. 12810 records from The Myxomycetes Collections at the Botanische Staatssammlung München - Collection of Hermann Neubert. 106 records from Arteninventar rund um den Rannahof. 334 records from Caracterización florística de la subcuenca del Río San Pedro, San Pedro, Valle del Cauca. 4 records from Nannofossil abundance of Hole 39-353A. 22 records from Nannofossil abundance of Hole 94-609B. 9 records from Diatom abundance measured on water bottle samples at station PS58/048-3. 48 records from Census of calcareous nannofossil taxa expressed as percent of total number of individuals counted, ODP Site 114-703. 12 records from (Table 4) Abundance of Pulleniatina obliquiloculata in sediment core ERDC-131BX. 142 records from Planktic foraminifera counts of sediment core V20-175. 5841 records from (Table 1) Ranges of Paleocene to middle Eocene planktonic foraminifera in ODP Hole 119-738B. 777 records from (Table 2) Distribution of benthic foraminifera in ODP Hole 120-748A. 11169 records from Akita Prefectural Museum:Hiroki Watanabe Collection of mollusca. 1368 records from Bird Collection of Yokosuka City Museum. 1498 records from Biogeographic distribution of Antarctic and sub-Antarctic Cumacea. 1808 records from Ant'Phipoda Database (New records). 2077 records from Vascular plant specimens of Iida City Museum. 138 records from Polychaetes in surface sediments off Sylt collected during Heincke cruise HE236. 578 records from Macrobenthos in surface sediments off Sylt collected during Heincke cruise HE293. 3359 records from (Appendix) Relative abundance of planktonic foraminifera in ODP Site 138-846 late Quaternary sediments. 36 records from Pollen profile from a swamp at Seelohe, Fichtelgebirge, Germany. 258 records from BIRDRACE Raumpatrouille Oriolus. 8 records from Diatom abundance measured on water bottle samples at station PS58/041-2. 5 records from Distribution of Quinqueloculina sp. in sediment core 13077-098. 18 records from Meiofauna abundance in sediment core 13200-012. 5276 records from Mamíferos de Nuevo León, México (UANL). 885 records from Asteroids from French subantarctic islands: records from the Marion Dufresne MD03 expeditions. 6 records from Collection Tunicata - ZIM Hamburg. 112 records from (Table 13) Distribution of Pleistocene to early Pliocene nannofossils in ODP Hole 108-667A. 18 records from (Table 1.2.2.1) Integrated abundance of sympagic meiofauna in sea-ice cores of Polarstern cruise ANT-XXIII/7. 168 records from (Table 2) Distribution of selected planktonic foraminifer species at ODP Site 124-770. 863 records from (Table 2) Distribution chart of dinoflagellate cysts and acritarchs from Angles, Southeast France. 82 records from The Bat Conservation Trust - Nathusius' pipistrelle survey. 1042 records from (Table 1) Relative abundances of Maastrichtian benthic foraminifera at El Kef, Part I. 40 records from (Table 3) Relative abundances of palynoclasts, palynomorphs and microplankton in ODP Leg 112 samples. 4277 records from Fundación Carl Faust: Herbario del Jardí Botànic Marimurtra: HMIM. 1422 records from Reconocimiento de la biodiversidad de la Reserva de la Biósfera Calakmul: Odonata, psocóptera y díptera acuáticos (Insecta). 65066 records from Formación de una base de datos y elaboración de un atlas de la herpetofauna de México. 2501 records from Helmintos parásitos de peces del sureste de México. 4 records from Pycnogonidea specimens of Kuroshio Biological Research Foundation. 134 records from National Feral Ferret (Mustela putoris furo) Database. 469 records from (Table 6) Stratigraphic ranges of selected Oligocene planktonic foraminifers in ODP Hole 115-710A. 1222 records from Ichneumonidae (Hymenoptera) de la reserva de la biosfera El Cielo, Tamaulipas. 601559 records from Watervogels - Wintering waterbirds in Flanders, Belgium. 476 records from Investigaciones sobre recursos no maderables de México: biología evolutiva y conservación de plantas del género Chamaedorea. 2091 records from Estudio florístico de las gramíneas de Zacatecas. 1218 records from Sistema de apoyo a la toma de decisiones para la reforestación rural en México. 7208 records from Catálogo y base de datos preliminar de la flora de Sinaloa. 1 records from Akita Prefectural Museum＋Specimens of Phylum Nemertea of Akita Prefectural Museum. 40923 records from Naturkundemuseum im Ottoneum Kassel, Entomological Collection. 3 records from Phytoplankton abundance measured on water samples from rivers of the Lena Delta in 2009. 1 records from Miriapodi di alcune grotte della Campania. 18473 records from Australian Antarctic Division Herbarium. 144 records from Endocast Collection -CONICET- Argentina. 9031 records from AIMS - LTM Nearshore Corals (OBIS Australia). 184 records from Relative abundance of T. quinqueloba in sediment core PS1243-1. 62592 records from Marine and Coastal Management - Linefish Dataset (Second Semester of 1997) (AfrOBIS). 1393 records from Rancho Grande. 8503 records from CBS Filamentous Fungi Database. 9208 records from AWI-Herbarium Marine Macroalgae. 504 records from Visual Plants (144.41.33.158) - Herbarium specimen from "USJ", Costa Rica. 8143 records from Distribution of planktic foraminifera of sediment core M35003-4. 1322 records from (Table 3) Percentages of planktonic foraminiferal species and varieties from the sediment surface samples from the South China Sea. 495 records from (Table A.08) Foraminiferal census data of sediment core PS1243-1 during marine isotopic stage 1-3 (80-150 µm). 20 records from (Table 2) Abundance and biomass of the main microplankton biota components in the Murmansk coastal pelagic zone in March 1998. 1665 records from (Table 11) Distribution of planktonic foraminifera in the early Miocene section of ODP Hole 149-900A. 203976 records from Swiss National Dragonflies Databank. 14165 records from NYSM Mammals. 1405 records from Fonoteca Zoológica, Museo Nacional de Ciencias Naturales, Madrid: FZ_AVES. 80742 records from Marine and Coastal Management - Linefish Dataset (First Semester of 1996) (AfrOBIS). 265 records from CNIN/Mantodea. 94510 records from TNHC Herpetology Collection. 364 records from Bird tissues, Division of Genomic Resources, UNM, Albuquerque, NM.. 30 records from Visual Plants (144.41.33.158) - Private collection of Manfred Kueppers. 19417 records from DSMZ Prokarya Collection Catalogue. 366 records from Marine fauna survey of the Vestfold Hills and Rauer Island, 1981-82. 194 records from (Table 2) Sea surface temperature reconstruction from sediment core MD88-770. 2955 records from (Table1) Abundance of planktonic foraminifera in DSDP Hole 75-532. 272 records from Coarse fraction analysis of sediment core PS1730-2. 980 records from Relative abundance of planktic foraminifera in the 120 kyr time slice reconstruction of sediment core RC08-145. 379 records from Relative abundance of planktonic foraminifera in sediment core MK-325. 1963 records from UCM Fish Collection (Arctos). 2078 records from (Table 1) Relative abundance of planktic foraminifera in Maastrichtian sediments of DSDP Hole 74-525A from the Walvis Ridge, South Atlantic Ocean. 494 records from Biologische Station im Kreis Wesel. 180 records from Entdeckertour am Muldestausee. 123 records from 4. GEO-Tag in Eberbach. 194 records from Pottundkopp. 93 records from Südwestlich der Parkwiesen. 142 records from Birdrace-Alte_Socken-Cuxhaven. 1 records from Streuobstwiese Alt Necheln. 12 records from Microplankton abundance at Station MARCH-1997-GN36199704601MSB01 in the euphotic zone of the Aegean Sea in spring 1997. Part 2 - dinoflagellates. 37 records from Occurrence of mammalia relicts at site Villa Seckendorff. 168 records from Occurrence of mammalia relicts at site Geißenklösterle. 11 records from Occurrence of mammalia relicts at site l´Abri Caminade-Ouest. 23 records from Occurrence of mammalia relicts at site Oblazowa 2. 32 records from Occurrence of mammalia relicts at site Jaskinia Niedwiedzia. 79 records from RSPB - Black grouse lek survey in Sutherland 2008-9 (RSPB). 541 records from Planktic foraminifera abundance of Hole 84-570. 56 records from Planktic foraminifera abundance of Hole 18-182. 347 records from Planktic foraminifera abundance of Hole 21-209. 1 records from Planktic foraminifera abundance of Hole 54-428. 539 records from (Table 1) Abundances of Discoaster species in ODP Hole 130-806C. 2087 records from Range table from planktonic foraminifers in ODP Hole 144-871A. 693 records from (Table 8) Planktonic foraminifer abundance of ODP Site 162-984. 31 records from Range table from planktonic foraminifers in ODP Hole 170-1042A. 182 records from Benthic foraminifera and algae abundance of Hole 81-554. 1 records from Dinoflagellate abundance of Hole 38-343. 168 records from Phytoplankton abundance in surface water in September 1996, Pisco, Peru. 1125 records from Benthic foraminifera of sediment core M25/4-KL13. 674 records from Relative abundance of dead benthic foraminifera in the small size fraction of surface sediment off NW Africa (Table 2). 1512 records from Benthic foraminiferal assemblages across the Cretaceous Paleogene boundray of ODP Site 208-1262 on Walvis Ridge, eastern South Atlantic. 7 records from Microplankton abundance in the euphotic zone of the Aegean Sea at Station JUNE-1998-MNB4. 12 records from New data on the European species of three genera Scelionidae (Hymenoptera).. 1 records from Range table from planktonic foraminifers in ODP Hole 174-1072A. 15 records from Range table from planktonic foraminifers in ODP Hole 192-1187A. 2259 records from Benthic foraminifera abundance of Hole 84-568, Part 1. 533 records from Range table from benthic foraminifers in ODP Hole 175-1076A. 56 records from Range table from benthic foraminifers in ODP Hole 144-874A. 258 records from Range table from benthic foraminifers in ODP Hole 144-877A. 304 records from Range table from benthic foraminifers in ODP Hole 160-967A. 345 records from Range table from nannofossils in ODP Hole 199-1218A. 42 records from (Tab. 10) Distribution of benthic foraminifera in Lower Cretaceous sediments of DSDP Hole 32-303A, Japanese Magnetic Lineations east of Japan. 105 records from Range table from dinoflagellates, acritarchs and prasinophytes in ODP Hole 160-966A. 1769 records from Distribution of benthic foraminifera in DSDP Hole 24-238 in the Central Indian Ocean (Appendix A). 2866 records from Departamento de Investigación y Experiencias Forestales de Valonsadero de la Junta de Castilla y León: JCYL-Fungi. 26 records from Phytoplankton abundance and species composition in the Gulf of Naples in March 1999 at Station MCSSI-phyto48-56. 1 records from Nothrus peltifer. 6 records from Die Milben in der Zoologischen Staatssammlung München. Teil 10. Überfamilie Crotonioidea (I). 67 records from (Table 2) Constituents of the sand-size fraction of ODP Site 139-857. 1 records from On centipedes (Chilopoda) of Albania, 2. 2465 records from Countryside Council for Wales - Bat Roosts Database - North West Wales. 5468 records from Orchid Herbarium Collection. 7 records from Occurrence of mammalia relicts at site Beckford. 428 records from Planktic foraminifera abundance of Hole 4-25. 427 records from Planktic foraminifera abundance of Hole 76-533A. 2135 records from (Table 1) Distribution of benthic foraminifers at DSDP Site 90-590. 8 records from Pollen and spore abundance of Hole 42-380. 4579 records from Estacion Biologica Donana - CSIC, Anfibios (EBD_HERP). 8000 records from Crustacean specimen detabase of Kanagawa Prefectural Museum of Natural History. 23408 records from Herbarium specimens of the Muséum d'Histoire Naturelle of Aix-en-Provence (AIX). 6328 records from Naturalis National Natural History Museum (NL) – Indo-Pacific Plio-Pleistocene fossils. 5 records from Studies on the Zoarcidae (Teleostei: Perciformes) of the southern hemisphere. IX. A new species of Pachycara from the southwestern Atlantic.. 14319 records from Irish Records from the Fungal Records Database of Britain and Ireland. 2 records from A new workerless inquiline in the Lower Attini (Hymenoptera: Formicidae), with a discussion of social parasitism in fungus-growing ants.. 331 records from (Table 2) Benthic foraminiferal genera in DSDP Core 95-612-37-3. 3201 records from Weevils of the Carpathians. 391760 records from The Flora of County Wexford. 7848 records from Lichen specimen database of Faurie collection. 23 records from New species of the plesiomorphic genus Nixonia Masner (Hymenoptera: Platygastroidea, Platygastridae) from South Africa.. 70 records from Instituto Nacional de Pesquisas da Amazônia - Porifera Collection. 1134 records from Alterra (NL) - Microarthropods inventory in European countries. 264 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Picidae. 1 records from Zetes dorsalis. 1581060 records from Bristol Regional Environmental Records Centre - BRERC October 2009. 156068 records from Molluscs collection (IM) of the Muséum national d'Histoire naturelle (MNHN - Paris). 1 records from Celaeno plicata. 1706 records from University of Amsterdam (NL) - Páramo pollen reference collection. 47499 records from Sphaeroceridae Collection. 223433 records from Phytochorologie des départements français. 89 records from Collection Crustacea - PUM. 165 records from Occurrence of the most important taxa of macrofauna on Voering Plateau, Tab.10b,11b,14b. 751 records from (Table T5) Planktic foraminiferal assemblages in sediments of ODP Hole 198-1212B, Shatsky Rise, Pacific Ocean. 796 records from (Data S1) Palynology of IODP Hole 318-U1356A. 1257 records from Faun. 424 records from Taxonomic Revision of the Ant-Acacias (Fabaceae, Mimosoideae, Acacia, Series Gummiferae) of the New World. 175 records from PSUZC-Rodents Collection. 7830 records from Mollusca Collection. 1 records from Pollen analysis of sediment profile TR0 from Truennensee. 184 records from (Table 2b) Biomass of macrobenthos species in samples from Cruise AMK54 stations in the Novaya Zemlya Trough. 3 records from Arthropoden aus südostalpinen Höhlen.. 2167 records from Otter Survey of Ireland 1982. 45809 records from Herpetology Collection - Royal Ontario Museum. 344 records from (Table T13) Planktonic foraminifera stratigraphy of ODP Hole 198-1211A, Zones Palpha-P3b. 74 records from (Table II) Abundance of epibenthic phyla and classes during RSS James Clark Ross cruise JR144. 5 records from Description of two new Temnothorax species (Hymenoptera: Formicidae) from Italy.. 1116766 records from Vegetation data from protected areas in Denmark (§ 3 in the Danish Nature Protection Act). 76124 records from Lichen field notes, Oslo (O). 43 records from Notes on the snake eels of the genera Apterichtus and Ichthyapus (Anguilliformes: Ophichthidae) of the Central and South Pacific, with the description of a new species.. 2775 records from (Table T4) Occurrence of Lower Cretaceous planktonic foraminifera in ODP Hole 171B-1050C. 1 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Formicariidae. 644 records from Thames Valley Environmental Records Centre - English Nature Oxfordshire Fen Survey 1990-1991 (A Comparative Survey of Rich Calcareous Fens of Oxfordshire) (as held by Thames Valley Environmental Records Centre). 49616 records from Nottinghamshire Biological and Geological Records Centre - UK abstract from Nottingham City Museums & Galleries (NCMG) Insect Collection Baseline database. 1 records from Oribates globulus. 4024 records from Sightings Map of Invasive Plants in Portugal. 457 records from Royal Horticultural Society - European Pear Rust (Gymnosporangium sabinae) monitoring. 1 records from Oribates calcaratus. 10137 records from Royal Horticultural Society - RHS lily beetle (Lilioceris lilii) monitoring . 240 records from Saproxylic beetles of the Po plain woodlands, Italy. 2 records from Amphibia ZMK. 50 records from (Table T3) Biogenic and mineral composition of sediments cored in Hamburg-Wulksfelde. 9787 records from Finnish Entomological Database: Hymenoptera. 25128 records from rmca-albertine-rift-butterflies. 1 records from Nothrus biciliatus. 120 records from Birdrace-Kosmos_Racer-Freising. 130 records from Schulgelände Gebrüder-Grimm-Schuleund Umgebung (Lingen). 149 records from Wirbach. 248 records from Herrensee-Gebiet (Fischbachtal im Odenwald). 104 records from Außengelände KITA "Mäuseburg" Waldkirchen. 163 records from Schulhof der Astrid-Lindgren-Schule Elmshorn. 47 records from Neanderthal. 28 records from Schulgelände Freiherr-vom-Stein-Gymnasium (Hamm). 21 records from "Natur macht Schule 2" Natur im Wohngebiet Gorndorf. 27 records from Wiese hinter der Schule (Darmstadt). 15 records from Kirchheller Heide ( Bottrop). 95 records from BIRDRACE BiBi. 30 records from Geführte Wanderung im Eselsbachtal. 52 records from Aktion der Klasse H2 in Simmelsberg. 128 records from Benthic foraminifera assemblage in sediment core BBLL2_MC4. 407 records from Abundance of benthic foraminiferal taxa for the Lower Oligocene of section Buchaugraben in the Lower Inn Valley area. 180 records from Assemblage of living benthic foraminifera in sediment core GeoB3701-1. 8 records from A revision of the South American species of the ant genus Probolomyrmex (Hymenoptera: Formicidae).. 98 records from Total foraminifera counts from M35/1_MSN1067. 26 records from Occurrence of zoobenthos organisms in the sampled Central-Yakutian Lakes, Appendix 2-4. 196 records from (Figure 4) Distribution of dinoflagellates in ODP Hole 129-802A. 10271 records from Carabidae of Poland. 122 records from (Table T1) Calcareous nannofossil stratigraphy of ODP Site 198-1213. 3416 records from Instituto Nacional de Pesquisas da Amazônia (INPA) - Opiliones Collection. 41 records from Scottish Natural Heritage - Site Condition Monitoring of Annex II Vertigo species in Scotland. 94 records from (Table 2) Distribution of Upper Cretaceous agglutinated benthic foraminifers in DSDP Hole 20-198A. 15 records from Additions to the ichthyofauna of the Tristan da Cunha Group, South Atlantic Ocean.. 477 records from Visfauna - Juvenile and adult fishes in riparian habitats along the river Leie. 42 records from (Table 2) Benthic foraminifers at DSDP Hole 72-515A. 225 records from (Table T2) Calcareous nannofossil stratigraphy of ODP Hole 198-1207B. 32 records from (Table T1) Dinoflagellate cyst and spore/pollen yield and preservation in ODP Leg 188 sites. 552 records from (Table 2) Relaticve abundances of Eocene to Oligocene planktonic foraminifera in ODP Hole 135-841B. 1 records from On the Chilopoda from Turkey. 50 records from A survey of the family Carabodidae C. L. Koch, 1836 (Acari: Oribatida). 7410 records from Helgeland Museum, Lepidoptera. 40530 records from Escarabajos Coprófagos (Coleoptera: Scarabaeinae) de la Colección Entomológica del Instituto Alexander von Humboldt. 55056 records from Biological Records Centre - Reptiles and Amphibians Dataset. 3650 records from Coelenterata (Cnidaria and Ctenophora) collection of National Museum of Nature and Science. 104 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Cathartidae. 4351 records from Portuguese Seaweeds. 3 records from A Partial Revision of the Genus Metabelba Grandjean (Oribatei, Acarina). 20 records from (Table 2) Counts of live (stained) benthic foraminifera from stations in the northern Gulf of California. 119366 records from The digitization of plant specimens of NTU. 9 records from Chenopodium vulvaria. 1 records from Oribates orbicularis. 1 records from Nothrus palliatus. 86 records from Besonderer Ort - besondere Natur: Die Mainzer Zitadelle. 135 records from Waldi-Weiher. 131 records from BIRDRACE Brut. 33 records from Assemblage of living benthic foraminifera in sediment core SO118_MC-35, 30-63 µm fraction. 61 records from Plasm bearing foraminifera counts of multinet M36/6_MSN1194. 118 records from Total foraminifera counts of multinet M21/2_MSN641. 24 records from Abundance, biovolume and biomass of heterotrophic dinoflagellates at station TT012_2-CTD1. 1 records from Microplankton counts and carbon biomass at station TT011_12-CTD150. 24 records from Distribution of meiobenthos in surface sediments of the northeastern Atlantic (Table 1). 482 records from Kühmark bei Wetzlar. 1 records from Cepheus ovalis. 9 records from Abundance of meroplankton during cruise BP00 (southern Kara Sea). 2 records from Abundance of broken diatom frustules measured on water bottle samples at station PS58/046-3. 45 records from BIRDRACE Ohne Graureiher läuft nix!. 1323 records from Estación Experimental de Zonas Áridas (CSIC), Almería: EEZA-Ungulados. 8784 records from Bryopytes specimens of Akita Prefectural Museum. 756 records from Targeting a portion of central European spider diversity for permanent preservation. 90399 records from CUMV Fish Collection (Arctos). 119 records from Various insect orders, NEF. 803 records from (Table 7) Relative abundances of stratigraphically useful planktonic foraminifers from ODP Hole 167-1020B sediments. 8 records from (Table 1) Major and minor element concentrations in the livers of polar bears (Ursus maritimus) from Canada, Alaska and Greenland. 105 records from Birdrace-ARKONAuten-Rügen. 44245 records from Cumbria Biodiversity Data Centre - Cumbria Biodiversity Data Centre. Vertebrate Observation Records, other than Birds. Pre-2010 for Cumbria . 63 records from Plasm bearing foraminifera counts of multinet SO118_MSN1253. 922 records from Phytoplankton abundance in surface water during cruise CD60. 75 records from Naturpark Kottenforst-Ville 19.6.09. 57 records from Range table from ostracoda in ODP Hole 151-910A. 1 records from Nothrus bistriatus. 1508 records from Spider (YCEM-SP). 132 records from (Table 9) Dinoflagellate cyst species distribution in ODP Hole 112-684B. 760 records from Arthropoda specimens of Toyama Science Museum. 30 records from (Table 6) Distribution of diatoms in Miocene to Pleistocene sediments of DSDP Hole 7-66. 210 records from (Table 3) Meiofauna density in surface sediments of the Cretan Sea. 877161 records from Finnish Winter Bird Census. 11300 records from Eastern Canada Benthic Macro Fauna (OBIS Canada). 2178 records from Flora exsiccata Bavarica. 7014 records from (Figure 6) Distribution of planktic foraminifera of ODP Hole 159-958A. 51 records from Planktic foraminifera assemblage in sediment core GIK23066-2. 11 records from Privatteich(St.Leon). 97 records from Birdrace-Die_Bonnapartemöwen-Rhein-Sieg-Kreis. 113 records from Hochschulgelände (Bremen). 32 records from Schulhof Sandhofenschule (Mannheim). 845 records from Planktic foraminiferal assemblages of the Paleocene-Eocene Thermal Maximum from ODP Hole 198-1209B, Shatsky Rise, Pacific Ocean. 7 records from Microplankton counts and carbon biomass at station TT008_5-CTD18. 21 records from Abundance of non-diatom phytoplankton measured on water bottle samples at station PS58/092-3. 192 records from Alterra (NL) - Microarthropods inventory in Cranendonck area. 127 records from Nannofossil abundance of Hole 78-541. 118 records from (Table S3) Coccolithophora in sapropel S1 of ODP Hole 160-964B, smear slide counts. 57 records from Nannofossil abundance in sediment core PS1313-4. 6 records from Phytoplankton abundance at station Rigel_3_2005-07 in July 2005, Chipana, Chile. 14 records from A review of the genus Mystrium (Hymenoptera: Formicidae) in the Indo-Australian region.. 14 records from Benthic macrofauna abundance of sediment core 13077-089. 777 records from Planktic foraminifera counts of sediment core RC17-108. 1030 records from Planktic foraminifera counts of sediment core V15-168. 19 records from Cottus kanawhae, a new cottid fish from the New River System of Virginia and West Virginia.. 30 records from (Table 2) Distribution of calcareous nannoplankton in selected samples of ODP Site 112-679. 86 records from Pollen analysis of sediment core GIK16856-2. 112 records from Abundance of macrobenthos organisms in the northern Wadden Sea in 2009. 500 records from Estudio taxonómico-florístico de la familia Orchidaceae en el Bajío: tribus Epidendrae y Maxillariae. 333 records from Revisión del género Zabrotes para México (Coleoptera: Bruchidae). 39 records from Regenrückhaltebecken Bad Bevensen. 179 records from Total foraminifera counts of multinet M21/6_MSN768. 24 records from Dinoflagellate cysts of sediment core IOW211670-7. 33 records from Phytoplankton abundance in surface water in 1998, Ancon, Peru. 4 records from Phytoplankton abundance at station Rigel_5_2005-08 in August 2005, Chipana, Chile. 62 records from Microzooplankton abundance measured on water bottle samples at station PS58/011-1. 9 records from Phytoplankton abundance at station Sechin_2003-12-10_1, Casma, Peru. 4 records from Abundance of nematoda in sediment profile M3/1_012 from the Iberian deep sea basin (Table 5). 33 records from Meiofauna abundances at the Arctic Håkon Mosby Mud Volcano (HMMV) of sediment core PS64/356-1. 1088 records from (Appendix 2-1) Distribution of planktonic foraminifera in late Neogene sediments of DSDP Site 7-62A in the western Pacific Ocean. 279 records from Koleopterologen am Bausenberg. 356 records from Biotope in Rheine - Aktion 350. 5 records from Nannofossil abundance of Hole 29-278A. 20 records from Nannofossil abundance of Hole 24-237. 5 records from Diatom abundance measured on water bottle samples at station PS58/049-3. 32 records from Nannofossil abundance in sediment core PS1312-4. 46834 records from Saltabel - Orthoptera in Belgium. 20 records from Distribution of planktonic foraminifera and other biogenic components in ODP Hole 113-693A (Figure 2). 40 records from Pollen record of sediment core Bokanjacko Blato 1. 321 records from Planktic foraminifera assemblage in sediment core GIK13289-1. 4044 records from Cactáceas Columnares de México (IE-MORELIA, UNAM). 6 records from Abundance and biomass of phytoplankton in Butakova Bay, Aral Sea, in september 1990. 201526 records from Field Museum of Natural History (Zoology) Insect, Arachnid and Myriapod Collection. 255 records from Planktic foraminifera counts of sediment core RC09-150. 95 records from Planktic foraminifera counts of sediment core RC17-73. 69 records from Planktic foraminifera counts of sediment core V19-19. 103 records from (Table 5) Distribution of calcareous nannofossils in ODP Hole 119-738C. 243 records from (Table 3) Distribution of planktonic foraminifera in the larger size fraction of ODP Hole 120-749B. 2069 records from Insect (JJHA-IN). 73 records from (Table 3) Distribution of calcareous nannofossils at ODP Hole 125-782A. 15 records from Molluscs in surface sediments off Sylt collected during Heincke cruise HE278. 142 records from Ostracoda in sediment core PS51/135-4. 1848 records from (Table 3) Occurrences of planktonic foraminifers in samples from ODP Hole 105-647A. 1 records from (Table 1.2.1.1) Abundance of sympagic meiofauna of sea-ice core PS69/567-1. 100 records from (Table 5) Abundance distribution of the 'clavate' subspecies of the genus Globigerinelloides and Pseudoschackoina saundersi in the Lesches en Diois section. 871 records from (Appendix D) Analyses of the benthic foraminifer assemblage at ODP Hole 112-680B. 15663 records from Collection Herpetologie - SNSD. 9649 records from Bolus Herbarium Algal Specimen Database (AfrOBIS). 9321 records from Marine and Coastal Management - Demersal Surveys (years 2006-) (AfrOBIS). 21619 records from Botanical Museum, Copenhagen. Database of type specimens. 4 records from Visual Plants (144.41.33.158) - Plants from Costa Rica; Annette Wolter. 426 records from Planktic foraminifera assemblage in sediment core GIK23419-8. 890 records from Percentages of planktonic foraminifera species in sediment core RC09-49. 523 records from Percentages of planktonic foraminifera species in sediment core V30-49. 169 records from Relative abundance of planktonic foraminifera in sediment core L-348. 211 records from Planktic foraminifera distribution of sediment core TRI172-22. 7 records from Analyses of the recent components of sediment core PS1402-2. 149 records from Biotop Binsenwiesen (Wehrheim/Taunus). 389 records from Planktic foraminifera abundance of Hole 23-228. 33 records from Planktic foraminifera abundance of Hole 16-161A. 167 records from (Table 6) Planktonic foraminifer species distribution, abundance, and preservation in DSDP Site 92-601. 9 records from Range table from planktonic foraminifers in ODP Hole 139-856C. 235 records from Range table from benthic foraminifers in ODP Hole 161-974B. 9 records from (Tab. 9) Occurence of microfossils in Late Jurassic sediments of DSDP Hole 36-330, Falcland Plateau. 3 records from Microfossil abundance of Hole 50-415. 51 records from (Table 4) Principal component analysis, paleotemperatures and distribution of infaunal benthic foraminifera in Late Quaternary sediments of core RC09-150 in the southeast Indian Ocean. 52 records from The high alpine bee fauna (Hymenoptera: Apoidea) of the Zillertal Alps, Austria. 3045 records from Obtención de la riqueza de aves y selección de especies susceptibles de monitoreo en la zona noroeste en el estado de Chiapas. 12772 records from UAM Invertebrate Collection (Arctos). 1271 records from (Table 14) Distribution of planktonic foraminifera in the late Oligocene section of ODP Hole 149-900A. 175 records from Unionids data from National Water Research Institute. 14484 records from iziko South African Museum - Shark Collection (AfrOBIS). 7880 records from Algaterra Types. 2000 records from Rust fungus specimen of Research Group of Plant Parasitic Fungi, Biosphere Resource Science and Technology, Graduate School of Life and Environmental Sciences, University of Tsukuba. 194 records from Distribution of planktic foraminifera of sediment core GIK23259-2. 75 records from Microplankton abundance in the euphotic zone of the Aegean, Levantine and Ionian Seas in March-April 1992. 129 records from Occurrence of mammalia relicts at site Bocksteinschmiede. 228 records from Occurrence of mammalia relicts at site Grotte Scladina. 1229 records from Centipedes of Ireland. 117 records from Planktic foraminifera abundance of Hole 72-515A. 420 records from Planktic foraminifera abundance of Hole 33-318. 43 records from Bryconops magoi and Bryconops collettei (Characiformes: Characidae), two new freshwater fish species from Venezuela, with comments on B. caudomaculatus (Gunther).. 9605 records from Aves Tanzanian collection at the Natural History Museum of Denmark (SNM). 11 records from (Tables S1,2) Stable isotopes in muscle tissue of polar bears (Ursus maritimus) from various regions of the Arctic. 14317 records from Nematodes collection (IN) of the Muséum national d'Histoire naturelle (MNHN - Paris). 1594 records from BoGART. 130 records from (Table S1) Pb/U zircon ages of ODP Hole 118-735B. 2084947 records from Naturalis Biodiversity Center (NL) - Botany Leiden. 11518 records from Merseyside BioBank - North Merseyside Insects (verified). 1 records from Hoplophora decumana. 130059 records from Inventaire National du Patrimoine Naturel : Mammifères de France. 17 records from Tierpark Zittau. 144 records from (Table 2) Absolute abundance, diversity, and relative abundance of benthic Foraminifera species in Upper Pleistocene - Holocene bottom sediments from Core Vulk-34-90. 28 records from (Table 7) Abundance of different Emiliania huxleyi cells in 0-25 m layer (upper mixed and thermocline layers) and in >25 m layer (under the thermocline) at Stations AH-2001-B3 and AH-2001-B3A. 11209 records from GBIF-PORTUGAL-Herbário João de Carvalho e Vasconcellos, I.S.A./U.T.L.. 16007 records from NCOS1959_Mollusca (OBIS China). 9 records from Analyses of the recent components of sediment core PS1217-1. 1269 records from Benthic foraminifera distribution of sediment core ASV11-858-3 (ASV 858). 173 records from A taxonomic review of the genus Myrmelachista (Hymenoptera: Formicidae) in Costa Rica.. 10 records from Microplankton abundance in the euphotic zone of the Aegean Sea at Station SEPT-1998-MNB6. 181 records from Occurrence of mammalia relicts at site Kemathenhöhle. 15 records from Occurrence of mammalia relicts at site Brühl 1. 82 records from Planktic foraminifera abundance of Hole 14-144A. 3413 records from Planktic foraminifera abundance of Hole 23-219. 841 records from (Appendix A3) Planktonic foraminifera of ODP Hole 166-1006A. 136 records from Planktic foraminifera abundance of Hole 63-468. 5733 records from (Figure 4) Occurrence of planktonic foraminifers and other selected constituents in samples from DSDP Hole 80-549A. 28 records from Hypostomus macushi, a new species of the Hypostomus cochliodon group (Siluriformes: Loricariidae) from Guyana.. 115 records from Range table from planktonic foraminifers in ODP Hole 155-931C. 14 records from Range table from planktonic foraminifers in ODP Hole 167-1010B. 88 records from Range table from planktonic foraminifers in ODP Hole 167-1021B. 152 records from Range table from planktonic foraminifers in ODP Hole 177-1088B. 3677 records from Christopher Walker collection of Glomeromycotan fungi. 172 records from Langes Tannen. 990 records from Distribution of major planktic foraminifer at Site 177-1091. 3 records from Beitrage zur Kenntniss paläarctischer Myriopoden. XV. Aufsatz: Lithobiiden aus Bosnien, Herzogovina und Dalmatien. 71 records from Foraminifera abundance of Hole 24-238. 85 records from Range table from planktonic foraminifers in ODP Hole 167-1022A. 50 records from Range table from benthic foraminifers in ODP Hole 160-969B. 129 records from Dinoflagellate abundance of Hole 81-552. 518 records from Relative abundance of benthic foraminifera in sediment core SO90-137KA. 405 records from Freiburger Netzwerk Artenvielfalt. 1 records from Abundance of benthos infauna at station GIK23062-2. 49812 records from Seaweeds of Ireland. 429 records from NODAI Culture Collection Center, Tokyo University of Agriculture, Japan. 233 records from Briòfits d'Andorra. 10985533 records from Norwegian Species Observation Service. 2146 records from William Nylander lichen collection. 216 records from (Figure 3) Distribution of latest Aptian and Cenomanian-Turonian planktonic foraminifers in DSDP Site 89-585. 403738 records from Marine Conservation Society - Seasearch Marine Surveys . 276 records from Environment Agency - Crayfish data update for Environment Agency Thames Region March 2009. 396 records from RSPB - 2008 Farmland Bird Survey North East Wales - RSPB/CCW. 4198 records from Planktic foraminifera (%) of sediment core MD96-2085. 336 records from (Table T3) Planktonic foraminifera stratigraphy of ODP Hole 198-1209A, Zones P5-P6b. 12 records from Six new, unusually small ants of the genus Leptomyrmex (Hymenoptera: Formicidae).. 1 records from Oribates flammula. 1419 records from Kangawalla Bird Sightings. 4 records from Arthropoden aus südostalpinen Höhlen.. 337366 records from British Lichen Society - BLS Lichen Database: England. 18 records from Range table from benthic foraminifers in ODP Hole 144-871A. 1460 records from Range table from benthic foraminifers in ODP Hole 151-909C. 420 records from Phytoplankton abundance in surface water in November 1997, Ilo, Peru. 6 records from Oberservation of birds at station PS14/146 along 49° West. 352271 records from New Mexico Biodiversity Collections Consortium database. 28420 records from Lichen Collection - University of Washington Herbarium (WTU). 7 records from Megafauna biomass in surface sediment during cruise PLG95A. 1167 records from Birds (KNAM-BI). 104 records from (Table 4) Distribution of Albian-Cenomanian nannofossils in DSDP Hole 77-540. 424 records from Mamíferos voladores y no voladores del suroccidente colombiano. 1137 records from (Appendix A) Distribution of planktonic foraminifera at DSDP Hole 72-516. 19 records from Contribution to the Central European Gymnodamaeus species G. barbarossa and G. bicostatus (Acari, Oribatida, Gymnodamaeidae. 29 records from Description of two new species of Hetereleotris (Gobiidae) from the south Pacific, with a revised key to species and synonymization of the genus Pascua with Hetereleotris.. 49 records from Additional records for Stenosagola newtoni Park & Carlton, 2013 (Staphylinidae: Pselaphinae: Faronitae), with notes on aedeagal morphology. 93 records from Nematode abundances in sediments from the Storegga Slide (Norwegian Sea) obtained during the VICKING expedition in 2006. 1 records from Die Chilopodenfauna Griechenlands. 2453470 records from Finnish Entomological Database: Lepidoptera. 708 records from RSPB - Black Grouse Trial Management Project Data, South-West and North Scotland, 2007-2012 (SNH, RSPB, FCS). 5583 records from All observations extracted from the Flora of Northumberland and Durham 1831. 218 records from (Table 6) Benthic foraminiferal genera in DSDP Core 95-612-5. 358 records from Apectodinium, age and percentage of endemic and bipolar dinoflagellate cysts of IODP Hole 318-U1356A. 1258 records from CMC_ornithology_GRC. 36657 records from Plant Specimen from Herbarium (LBG) in China, Lushan Botanical Garden, Jiangxi and Chinese Academy of Sciences. 69396 records from ECatSym: Electronic World Catalog of Symphyta. 694766 records from Royal Botanic Garden Edinburgh Herbarium (E). 9 records from The Maugean Skate, Zearaja maugeana sp. nov. (Rajiformes: Rajidae) - a micro-endemic, Gondwanan relict from Tasmanian estuaries.. 1 records from Arthropoden aus südostalpinen Höhlen.. 18 records from (Table 2) Abundance, wet biomass, and carbon biomass of all major groups and total phytoplankton in the upper and lower parts of the desalinated water lens and in the layer under the lens in the Kara Sea. 12888 records from MfN - Fossil Fish Collection. 85516 records from Botanical Society of the British Isles - Changing Flora of Glasgow 1982-2000. 3 records from Trichomycterus santanderensis: A new species of troglomorphic catfish (Siluriformes, Trichomycteridae) from Colombia.. 102 records from (Figure 3) Selected benthic foraminifera measurements from sediment core AvH248260-1, Ameralik Fjord, SW Greenland. 12516 records from Anymals+plants - Citizen Science Data. 17035 records from Tromsø Museum, Lichens. 97 records from New distributional data on aquatic and semiaquatic bugs (Hemiptera: Heteroptera: Gerromorpha & Nepomorpha) from South America. 26 records from A new species of the Asian schilbid catfish genus Clupisoma from Myanmar, with a redescription of Clupisoma prateri Hora (Osteichthyes: Siluriformes: Schilbidae).. 959 records from RSPB - Black-throated diver national surveys in Scotland (SCARABBS). 618 records from RSPB - Scottish Crossbill National Survey in the UK in 2008 (SCARABBS). 7873 records from Bedfordshire and Luton Biodiversity Recording and Monitoring Centre - Bedfordshire Himalayan Balsam Surveys (WT) - 2010-2012. 27 records from A new species of Astyanax (Teleostei, Characiformes, Characidae), with breeding tubercles, from the Paraná and Uruguay river basins.. 9879 records from Bibliographic records of Angola mammals. 857 records from Field Study Group of the Dutch Mammal Society (NL) - 2004 - Mammal Survey Rakitovec, Slovenia. 31748 records from Colección Nacional de Aracnología - Museo Argentino de Ciencias Naturales 'Bernardino Rivadavia'. 54 records from Zentralfriedhof (Wien). 1738 records from (Table 2) Relative abundance of planktonic foraminifera species in Pliocene - Early Quaternary sediments from ODP Hole 111-677A. 14882 records from NCSM Mammals Collection. 4685 records from Registros biológicos de especies de fauna vertebrada terrestre en las centrales de San Carlos y Jaguas - 2006. 164 records from Planktonic foraminifer occurrences and zonations from IODP Hole 313-M0029A. 51 records from Towards the conservation of parasitoid wasp species in Canada: Preliminary assessment of Microgastrinae (Hymenoptera: Braconidae). 1172 records from (Table T1) Benthic foraminfera stratigraphy of ODP Hole 199-1215A sediments. 239 records from Systematic review of the neotropical shovelnose catfish genus Sorubim Cuvier (Siluriformes: Pimelodidae).. 965 records from Thames Valley Environmental Records Centre - Nature Conservancy Council Oxfordshire Fen Survey 1983 (as held by Thames Valley Environmental Records Centre). 367 records from Clyde River Foundation - Twaite Shad (Alosa fallax) distribution for Scotland, historical to present. 2824 records from Fundación Miguel Lillo - Colección Invertebrados. 15 records from (Table 1) Occurrence and abundance of late Early Cretaceous radiolarians at DSDP Hole 62-463. 1127 records from Census of the secondary forests of the Lama forest reserve (Southern Benin). 64 records from Wiese - Schulgelände des Franziskusgymnasiums (Lingen). 97 records from BIRDRACE NABUhu Trier!. 125 records from Plasm bearing foraminifera counts from M35/1_MSN1043. 49 records from Total foraminifera counts of multinet M10/2_MSN238. 72 records from Plasm bearing foraminifera counts of multinet M21/1_MSN603. 159 records from Total foraminifera counts of multinet M21/6_MSN789. 65 records from Distribution of planktic foraminifera (125-250 µm) of box sediment core PS1246-2. 6065 records from LISU Herbario Angola. 31000 records from Plant Specimen Database of Tama Forest Science Garden, Forestry and Forest Products Research Institute, Japan. 52381 records from UAM Herbarium (ALA), Cryptogam Collection (Arctos). 16195 records from People's Trust for Endangered Species - Hedgehog records 2005-2006: Hogwatch and Rural Landowner surveys. 29 records from Potential indicator species of climate changes occurring in Québec, Part 1: the small brown lacewing fly Micromus posticus (Walker) (Neuroptera: Hemerobiidae). 195 records from (Table T3) Planktic foraminiferal assemblages in sediments of ODP Hole 198-1210A, Shatsky Rise, Pacific Ocean. 2 records from Succession of benthic hard-bottom communities abundance at X-Huinay in 2010. 12 records from (Appendix B) Stratigraphic occurrence of radiolarian special and species groups in sediments of ODP Hole 199-1218A. 693 records from (Figure 2e) Distribution of planktonic foraminifera in bottom sediments of Core Vy20-3205. 45 records from Université Pédagogique Nationale de Kinshasa (UPN) - Le bétail dans la République Démocratique du Congo (bases de données des animaux élevés pour consommation)- Projet CABIN. 128787 records from Seed and Leaf Beetle Recording Scheme - Bruchid and Chrysomelid Distributions in Britain and Ireland: pre 1900, 1900-1979, 1980 onwards. 102 records from Birdrace-Westfälische-Nachtigallen-Recklinghausen. 106 records from Schulgarten Hans-Carossa-Oberschule. 17 records from Bachrenaturierung Littfe. 12 records from Art´n Vielfalt im Kinderwald. 123 records from Total living benthic foraminifera at station M33/1_MC-19 (CAST), size fraction >30 µm. 50 records from Assemblage of total living benthic foraminifera in sediment core SO129_MC-03. 1120 records from Dpto. de Zoologia y Antropologia Fisica, Universidad de Murcia. 66 records from BIRDRACE Die schrägen Vögel aus dem Sauerland 2. 195 records from Total foraminifera counts from multinet M31/3_MSN923. 84 records from (Table 4) Morphologic variability in the Globorotalia puncticulata group and abundances of dominant species at DSDP Hole 80-548. 195 records from (Table T2) Concentrations and accumulation rates of Globorotalia menardii at ODP Hole 175-1087A. 306 records from Size of planktic foraminifera at CTD station PS55/037. 323 records from Size of planktic foraminifera at CTD station PS55/083-1. 1683 records from (Appendix 2) Distribution of planktonic foraminifera in the last 70 kyr of sediment core MD95-2043 from the western Mediterranean Sea. 3 records from Size fractioned abundances and carbon biomasses of heterotrophic protists at station NIOP-B2_820-4. 24 records from Abundance and carbon biomass of phytoplankton at station TT007_6-CTD73. 7 records from Sarcodine counts and carbon biomass at station TT008_5-PMOC2. 8 records from Microzooplankton abundance and biomass at station NBP97-03-16-1. 10 records from Phytoplankton abundance during Arnold Veimer cruise AV90/2. 80889 records from Scottish Natural Heritage - Standing Waters Database. 16 records from Meiofauna abundances at the Arctic Håkon Mosby Mud Volcano (HMMV) of sediment core PS64/313-1. 4 records from Zwischen Enz und Schule. 369 records from (Table 1) Coccolith percentage of surface sediment samples from the south-eastern South Atlantik. 92061 records from Herbarium (ICEL). 33 records from Schüler erforschen die Helme-Aue. 43 records from Plasm bearing foraminifera counts of multinet M42/3_MSN1369. 35 records from Planktic foraminifera of sediment core GeoB1404-3. 24 records from Abundance, biovolume and biomass of heterotrophic dinoflagellates at station TT012_4-CTD8. 3 records from Sarcodine counts and carbon biomass at station TT008_6-PMOC7. 141 records from Pfingstexkursion Alter Bessin. 90 records from Relative abundance of coccosphere-units of site GIK23259. 411 records from Coccolith percentage of surface sediment samples. 238 records from Coccoliths in ODP Hole 104-643A. 104 records from Ross Sea Pycnogonids. 781 records from (Table 2) Benthic foraminiferal assemblage in the early Pleistocene interval of ODP Site 162-984. 268 records from (Table 5) Relative abundance of benthic foraminifera in ODP Hole 112-686A. 415 records from (Table 1) Distribution of Lower Cretaceous calcareous nannofossils in ODP Hole 113-692B. 20 records from (Table 1) Occurrences of ostracodes in ODP Hole 122-761B. 7245 records from (Figure 5) Stratigraphic ranges of selected planktonic foraminifers at ODP Hole 101-627B. 3472 records from Cnidarios, poliquetos, crustáceos (decápodos) y quetognatos pelágicos del Golfo de California. 2342 records from La etnobiología de los recursos nutritivos en las comunidades Tzeltales en los Altos de Chiapas. 431 records from Bee specimens. 4660 records from Distribution of planktonic foraminifera of site GeoB1105. 45 records from Range table from planktonic foraminifers in ODP Hole 182-1130C. 174 records from Total foraminifera counts from multinet M31/3_MSN915. 11 records from Large protozoa abundance measured on concentrated water bottle samples at station PS58/088-7. 3 records from Sarcodine counts and carbon biomass at station TT011_6-CTD71. 21 records from Abundance of non-diatom phytoplankton measured on water bottle samples at station PS58/011-3. 5352 records from Benthic foraminifera abundance in per cent of Hole PRAD1-2. 4 records from Distribution of meiobenthos in sediment core M23_123 (2) of the northeastern Atlantic (Table 1). 15 records from Pollen profile 2 from Richland Creek. 89 records from (Table 2) Abundance of benthic foraminifers of sediment core PS2139-1. 53 records from Benthic foraminifera and phytodetritus species in sediments from DSDP Site 85-573. 4014 records from Herpetological specimens. 456 records from Øvre Heimdalsvatn, Radiocaesium (Cs-137) monitored annually in brown trout (Salmo trutta). 1634 records from ZFMK DORSA. 65 records from Nannofossil abundance of Hole 64-475. 11 records from Nannofossil abundance of Hole 15-153. 8 records from Nannofossil abundance of Hole 10-88. 4 records from Nannofossil abundance of Hole 16-156. 2 records from Nannofossil abundance of Hole 1-4. 6494 records from Open Mosaic Habitat Survey Group - Invertebrates recorded during Open Mosaic Habitat survey in England and Wales (2012). 2 records from Nannofossil abundance of Hole 75-530A. 108 records from Planktic foraminifera counts of sediment core RC08-39. 440 records from Antarctic and Subantarctic Asteroid zoogeography. 58 records from Collection Cnidaria - ZIM Hamburg. 2599 records from Collection Ornithologie - ZSRO. 1 records from Mesozoa - SMF. 9 records from Component analysis of TV-guided grab sampler GeoB10071-3. 2291 records from Bird Collection. 24 records from Large protozoan and small metazoan abundance measured on concentrated water bottle samples at station PS65/591-11. 3468 records from Assemblage of dinoflagellate cysts analysed in sediment core SO78-158-1. 6 records from Nano and microzooplankton abundance and biomass at station NBP97-01-02-2. 57 records from Microzooplankton abundance measured on water bottle samples at station PS58/091-4. 521 records from Schanzenanlage Bergham. 1151 records from Coccolithophores in surface sediments of the Arabian Sea (TAble 1). 448 records from Geometry of coccolith Gephyrocapsa in sediment core GIK23062-1. 16 records from Nannofossil abundance of Hole 37-332B. 10 records from Nannofossil abundance of Hole 38-338. 7319 records from Coleoptera. 14 records from Nannofossil abundance of Hole 49-412. 13 records from Nannofossil abundance of Hole 11-103. 16 records from Nannofossil abundance of Hole 11-106B. 15 records from Benthic macrofauna abundance of sediment core 13078-013. 42 records from Macrofauna biomass in surface sediment sampled during cruise DI237. 14 records from Relative abundance of live benthic foraminifera of sediment core M5/2_91MC. 3290 records from (Figure 8) Range chart of selected dinocysts and acritarchs of ODP Hole 104-644A cores 15-35. 15 records from (Table 2.2.1.1) Abundance of sympagic meiofauna of sea-ice core IO-2. 27 records from Pliocene/Pleistocene benthic foraminiferal abundances from ODP Hole 161-975D. 3 records from Pollen record of profile 1TZ1. 186 records from Total foraminifera counts from multinet SO119_MSN1283. 5 records from Revision der Ceratozetidae, Ceratozetes peritus Grandjean (Arach., Acari, Oribatei). 2 records from Nannofossil abundance of Hole 1-4. 2 records from Nannofossil abundance of Hole 3-14. 16 records from Nannofossil abundance of Hole 24-235. 5 records from Distribution of Quinqueloculina sp. in sediment core 13200-078. 230 records from Planktic foraminifera counts of sediment core V27-60. 146 records from (Table 2) Expected and observed beluga (Delphinapterus leucas) sightings according to habitat characteristics. 10 records from (Table 2b) Nannofossil distribution chart of ODP Hole 122-761B. 1301 records from Collection Hymenoptera SMF. 727 records from Flora acuática vascular del área focal Felipe Carrillo Puerto, Corredor Biológico Sian Ka'an-Calakmul, Quintana Roo, México. 14194 records from Computarización de las colecciones de vertebrados terrestres de la Escuela Nacional de Ciencias Biológicas, IPN Fase 1: Estado de México, Hidalgo, San Luis Potosí y Tlaxcala. 38 records from (Table 1) Chiasmolithus species and intermediate forms of ODP Holes 105-647A and 120-748B. 846 records from (Table 2) Relative abundances of stratigraphically useful planktonic foraminifers from ODP Hole 167-1011B sediments. 5224 records from Insect Specimens of Omogo Mountain Museum. 138 records from Visual Plants (144.41.33.158) - Herbarium specimen from "BIEL", Germany. 365 records from Bird Specimens of Miyazaki Prefecture Museum of Nature and History. 289 records from NSG Hülenbuch Hörnle (Tieringen/Meßstetten). 124 records from Occurrence of mammalia relicts at site Pod hradem. 397 records from Planktic foraminifera abundance of Hole 2-10. 170 records from (Table 4) Planktonic foraminifer species distribution, abundance, and preservation in DSDP Site 92-599. 14 records from Range table from planktonic foraminifers in ODP Hole 159-962B. 15 records from Urwald 2 (Bad Waldsee). 156 records from (Table 2) Distribution of some benthic foraminifera in ODP Hole 108-658A. 19 records from (Table 12) Distribution of calcareous nannoplankton in selected samples of ODP Hole 112-688E, Part I. 181 records from (Table 3) Range chart of calcareous nannofossils in ODP Hole 122-763B. 23 records from (Table 4) Relative abundance of the major nannofossil groups in the Lower Cretaceous of ODP Hole 113-693A. 10 records from (Table 3) Minerals and components of sediments from DSDP Site 94-609_Site, North Atlantic. 13 records from (Table 2f) Nannofossil distribution chart of petroleum well Montara-2. 16 records from Pollen data of trap CB4. 118 records from Abundance of macrobenthos organisms in the northern Wadden Sea in 2010. 84 records from Fig. 3. Pollen record of profile PG1228 from lake Levinson-Lessing. 2123 records from Diversidad de peces de las lagunas costeras de Pueblo Viejo y el Mango, Veracruz. 517 records from Inventario de los murciélagos de los parques nacionales Sierra de San Pedro Mártir y Constitución de 1857, Baja California, México. 515 records from (Table 2) Neogene benthic foraminifers of ODP Hole 120-748B. 342 records from (Table 1) Dinoflagellate cysts and acritarchs in upper Pliocene and Pleistocene sediments from ODP Hole 151-911A. 3 records from Pollen analysis of surface samples near sediment core Fiekers Busch. 62324 records from Herbarium Specimens of Museum of Nature and Human Activities, Hyogo Pref., Japan. 6010 records from Abundance of benthic infauna in surface sediments from the North Sea sampled during HEINCKE cruise HE133. 364 records from Nekton and plankton counts from neuston net (300 µm) hauls of cruise GAE 1975/76. 491 records from (Table 1) Relative abundances of planktic foraminifers in bottom sediments from Core AMK4-316GC. 346511 records from ARGOS Satellite Tracking of animals. 1888 records from REVIZEE South Score / Pelagic and Demersal Fish Database (OBIS South America, BRAZIL). 11224 records from Fungi collection of Jyväskylä University Museum. 1221 records from NBM Unionoids. 174617 records from Banc de dades de biodiversitat de Catalunya-VerteCat. 28934 records from Coleção de Abelhas do Museu de Ciências e Tecnologia da PUCRS. 238 records from Ophion scutellaris species group specimen data. 198 records from Planktic foraminifera assemblage in sediment core GIK23056-1. 4456 records from Colección de Artrópodos de la Asociación BIGA para el estudio del patrimonio natural de Galicia: ABIGA. 22 records from Sediment properties of core PLG95B_06BOXG. 5157 records from (Table A.01) Planktic foraminiferal census data of sediment core GIK23414-6. 35 records from The ant genus Tetraponera in the Afrotropical region: the T. grandidieri group (Hymenoptera: Formicidae).. 1913 records from (Appendix B2) Distribution of planktic foraminifera in ODP Hole 181-1125A east of New Zealand. 92 records from Zwei Flüsse - eine Stadt (Villingen-Schwenningen). 148 records from Hintere Halde. 2303 records from Distribution of planktonic foraminifera in surface sediment samples A180-072 to V23-83. 49 records from Checklist of Fishes from Madagascar Reef, Campeche Bank, México. 251 records from Foraminifera abundance of sediment core IN68-28. 98 records from Occurrence of mammalia relicts at site Felsställe. 5 records from Range table from planktonic foraminifers in ODP Hole 151-912A. 246 records from Benthic foraminifera abundance of Hole 73-524. 14 records from Benthic foraminifera abundance of Hole 42-378. 61 records from Dinoflagellate abundance of Hole 22-214. 11 records from Oberservation of birds at station PS14/142 along 49° West. 35489 records from MEXU/Colección de Plantas Acuáticas. 1232 records from Universidad de Málaga: MGC-Briof. 52 records from Abundance of epibenthic echinoderms at seafloor photography station PO196_1018. 101480 records from Scottish Environment Protection Agency - River macroinvertebrate data for 2005 and 2006. 73 records from (Table 17) Calcareous nannofossil occurrences in ODP Hole 130-804C. 1 records from Zetes pallidulus. 6757 records from Anillamiento de Aves Sierra Nevada de Santa Marta - Proyecto Cruzando el Caribe. 872 records from Colección de Entomología - Hymenoptera - Parasitica. 9161 records from Palaeobiology - Vertebrate Comparative Osteology Collection - Royal Ontario Museum. 17520 records from Arthropod collection, Tromsø Museum. 491 records from John Muir Trust - Plants, Bryophytes and Lichens recorded on the Nevis Estate during summer 2003.. 3253 records from ISU Birds. 1 records from Über einige von Jaroslav Storkán in Bulgarien gesammelte Chilopoden. 31 records from Phytoplankton abundance and species composition in the Gulf of Naples in March 1999 at Station MCSSI-phyto39-47. 399 records from Distribution of planktic foraminifera (125-250 µm) of sediment core GIK17732-1. 5 records from Analyses of the recent components in the sand fraction of sediment core PS1422-1. 167 records from Artenvielfalt auf den Elbwiesen (Dessau). 2475 records from Artenvielfalt auf der Weide - GEO-Hauptveranstaltung in Crawinkel. 10 records from Microplankton abundance in the euphotic zone of the Aegean Sea at Station JUNE-1998-MNB5. 1 records from Die vom k. k. Oberartze Herrn Dr. Justyn Karlinski im Jahre 1887 in Bosnien, der Herzegowina und in Novibazar gesammelten Myriopoden. 107 records from Planktic foraminifera abundance of Hole 18-180. 237 records from Planktic foraminifera abundance of Hole 32-305. 303 records from National Botanic Garden Belgium - Martius. 21 records from Range table from planktonic foraminifers in ODP Hole 139-855B. 1592 records from Range table from planktonic foraminifers in ODP Hole 139-856A. 1686 records from Range table from planktonic foraminifers in ODP Hole 159-960C. 180 records from Range table from planktonic foraminifers in ODP Hole 180-1115C. 1066 records from Benthic foraminifera abundance of Hole 80-549A. 84 records from Range table from benthic foraminifers in ODP Hole 172-1059B. 24 records from Range table from benthic foraminifers in ODP Hole 192-1185B. 1024 records from Benthic foraminiferal assemblages (living), surface data. 76 records from Live (Rose Bengal stained) benthic foraminifera from surface sediments of the Indian and Pakistan continental margin (Table 1). 19610 records from Colección del Departamento de Biología Animal (Zoología) de la Universidad de La Laguna. 37807 records from Collection Crustacea SMF. 1 records from Abundance of benthos infauna at station GIK23037-3. 1 records from Abundance of benthos infauna at station GIK23038-1. 7 records from An unusual new species of Micraspis Chevrolat (Coleoptera: Coccinellidae) from northeastern India. 1287 records from RAVON (NL) - Fish observations extracted from Hoek (1888) and Hoek (1897). 20 records from Microplankton abundance in the euphotic zone of the Cretan Sea at Station OCTOBER-1995-D4. 66 records from Occurrence of mammalia relicts at site Malerfels_I. 54 records from Occurrence of mammalia relicts at site Rusenschloß. 48 records from Planktic foraminifera abundance of Hole 6-47. 484 records from Foraminifera abundance of Hole 74-529. 49 records from Planktic foraminifera abundance of Hole 15-147C. 50 records from Planktic foraminifera abundance of Hole 60-457. 105 records from Range table from planktonic foraminifers in ODP Hole 155-942C. 374 records from Relative abundance of dead benthic foraminifera of sediment core M5/2_91MC. 75352 records from Universidad de Málaga: MGC-Cormof. 3471 records from Collection Foraminifera SMF. 7 records from Inventario de Murciélagos en la Finca la Reserva, El Perico, Yopal, Casanare. 249 records from Herbarium of the Department of Natural Forests (Forest Research Institute) - Lichens. 316 records from Hymenoptera, NEF. 14522 records from MVZ Egg and Nest Collection (Arctos). 17 records from (Table 4) Total phytoplankton biomass, biomass of certain algal groups in the upper mixed layer and the water column, and contribution of the algal groups to total biomass of phytoplankton in the southwest Kara Sea on August 9-12, 2007. 111991 records from Monitoring data from the federal state North Rhine-Westphalia (Germany). 6 records from (Table 2) Miocene biostratigraphy of the Vierlandian stage in Schleswig-Holstein. 4599 records from (Table 3B) Occurrence and estimated abundance of planktonic foraminifers at DSDP Holes 85-572C and 85-572D. 534510 records from Naturalis Biodiversity Center (NL) - Botany Wageningen. 4 records from Arthropoden aus südostalpinen Höhlen.. 30327 records from Thames Valley Environmental Records Centre - Nature Conservancy Council Survey of Ancient Woodlands in Berkshire.. 30 records from Riekdahler Wiesen. 516 records from Occurence of microfossils in Early Cretaceous sediments of DSDP Hole 25-249 (Tab. 1). 6 records from (Table 1) Dinoflagellate cyst zonations at ODP Site 202-1233. 214 records from NSG Haunestausee, Hauneteiche. 90 records from Collection Ctenophora SMF. 26 records from Composition of benthic macrofauna in surface sediments of the east Greenland continental slope (75° N section). 492869 records from Precis Plant Data. 335 records from Revision of the South American freshwater genus Plagioscion (Teleostei, Perciformes, Sciaenidae).. 116772 records from Plant Specimen from Herbarium (IBK) in China, Guangxi Institute of Botany, Chinese Academy of Sciences. 31841 records from Birds collection (ZO) of the Muséum national d'Histoire Naturelle (MNHN - Paris). 2753 records from (Figure 8 a) Distribution of Cretaceous planktonic foraminifers and associated organisms from DSDP Hole 77-535. 621 records from Biological Records Centre - UK Ladybird Survey data from iRecord . 70 records from Instituto Nacional de Pesquisas da Amazônia - Porifera Collection. 1 records from Arthropoden aus südostalpinen Höhlen.. 304 records from Succession of benthic hard-bottom communities abundance at station Errina2012_IS_solar2. 78 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: géneros Saltator & Saltatricula. 103310 records from Plant Specimen from Herbarium (CDBI) in China, Chengdu Institute of Botany, Chinese Academy of Sciences. 365 records from Colección Herpetológica de la Patagonia. 27079 records from Colección de Aves de Colombia del Instituto Alexander von Humboldt. 7 records from Kryptolebias sepia n. sp. (Actinopterygii: Cyprinodontiformes: Rivulidae), a new killifish from the Tapanahony River drainage in southeast Surinam.. 110 records from Birdrace-Göttinger_Sozialbrachvögel-Göttingen. 118 records from BIRDRACE Die Lippegeier. 35 records from Assemblage of living benthic foraminifera in sediment core SO118_MC-51, 30-63 µm fraction. 206 records from Total foraminifera counts from multinet M31/3_MSN908. 15 records from Pollen analysis of sediment profile MU1 from Muggesfelder See. 33 records from Bedfordshire and Luton Biodiversity Recording and Monitoring Centre - Bedfordshire Stylops (BNHS) â 1930-1971. 4591 records from WII Herbarium Dataset. 6319 records from Colección de anfibios y reptiles del Laboratorio de Herpetología de la Universidad del Valle (UV-C). 1197 records from Hertfordshire Biological Records Centre - Hertfordshire Urban Surveys (incomplete). 12 records from (Table IV) Abundance of isopoda families during RSS James Clark Ross cruise JR144. 55305 records from CUMV Bird Collection (Arctos). 5709 records from Coleoptera of Piska Forest. 1 records from Descriptions de nouvelles fourmis éthiopiennes (quatrième note).. 68 records from (Table 8) Abundance of silicoflagellates and ebridians in selected samples from ODP Hole 138-851B. 3 records from On two Italian Lithobius species described by Silvestri, with taxonomic notes on the genus Eupolybothrus Verhoeff (Chilopoda, Lithobiida). 73 records from (Table 7) Abundance of silicoflagellates and ebridians in selected samples from ODP Hole 138-850B. 3459 records from Hymenoptera collection (EY) of the Muséum national d'Histoire naturelle (MNHN - Paris). 1612 records from (Figure 8b) Distribution of Cretaceous planktonic foraminifers, calpellionids and associated organisms from DSDP Hole 77-535. 33 records from Phytoplankton abundance and species composition in the Gulf of Naples in March 1999 at Station MCSSI-phyto57-65. 19522 records from Wildbook for Whale Sharks. 638 records from EcoRecord - Fish records held by EcoRecord for the Birmingham and the Black Country area collated prior to March 2013. 23 records from Alter Nördlicher Friedhof (München). 53 records from Weidegut Rechab. 86 records from Naturerlebnisraum Koppelsberg (Plön). 101 records from BIRDRACE nabu-rhein-main.de. 1034 records from (Table 3) Distribution of Campanian-Maestrichtian calcareous foraminifers in DSDP Hole 78-543A. 1 records from Deux especes nouvelles pour la science du genre Eupolybothrus Verhoeff (Lithobiomorpha: Ethopolinae). - Two new species for the science in the genus Eupolybothrus Verhoeff (Lithobiomorpha: Ethopolinae). 146382 records from Swedish Board of Fisheries (Fiskeriverket) - Institute of Coastal Research. 96 records from Trichoptera (caddisflies) of Ireland. 176 records from Abundance of phytoplankton, heterotrophic nanoflagellates and bacteria through the water column at time series station L4 in the Western English Channel in 2010. 11762 records from Chrysomelidae of the Carpathians. 209 records from (Table 2) Ostracoda community from DSDP Hole 95-613. 55 records from Von A(horn) bis Z(ecke) des WWP Chemnitz. 263 records from Artenvielfalt Kreis Gießen. 101 records from Naturhausgarten. 31 records from Regenwasserabfangbecken. 28 records from Stadtpark Prinzengarten (Sigmaringen). 132 records from BIRDRACE Die Wetterauer. 545 records from Benthic foraminiferal assamblage in the >125 micron fraction of sediment core PS1745-5 (Table 8). 23 records from Assemblage of living benthic foraminifera in sediment core CD146_55918#7, 63-150 µm. 24 records from A new species of Bedotia (Teleostei: Atherinomorpha: Bedotiidae) from the Rianila drainage of Eastern Madagascar, with redescriptions of Bedotia madagascariensis and Bedotia geayi.. 97 records from Total foraminifera counts from M35/1_MSN1061. 49 records from Total foraminifera counts of multinet FCA97C_MSN1345. 482 records from Total foraminifera counts of multinet M6/7_MSN91. 74 records from Distribution of planktic foraminifera (250-500 µm) of box sediment core GIK23059-2. 24 records from Abundance, biovolume and biomass of heterotrophic dinoflagellates at station TT012_5-CTD35. 3 records from Sarcodine counts and carbon biomass at station TT007_9-CTD108. 8 records from Phytoplankton abundance at station Casma_2003-01-30_2, Casma, Peru. 2 records from Beitrage zur Kenntniss paläarctischer Myriopoden. XV. Aufsatz: Lithobiiden aus Bosnien, Herzogovina und Dalmatien. 3 records from (Table 2) Upper Eocene silicoflagellates from DSDP Hole 95-612. 132 records from (Table 1) Relative abundances of benthic foraminifera in ODP Site 128-798C. 2303 records from (Appendix) Dinoflagellate abundance in ODP Site 202-1233. 1 records from Oribates angulatus. 34 records from Caddisfly Records, Edenvale, Co. Wexford 2010. 111 records from Birdrace-Uhulogen-Lippe. 192 records from Steinbruch Mainz-Weisenau, 2. Jahr. 22 records from Kuhwiese Beerentaltrift (Hamburg/ Harburg). 5 records from Gewässeruntersuchung (Prien) mit Kl. 4b. 101 records from BIRDRACE Enger am Spektiv. 123 records from BIRDRACE INTERNETLITHO feat Fliegende Füchse. 11 records from Umgebung Jugendherberge Clausthal, Klasse 8d. 87 records from Stable isotopes measured on Ammonia beccarii from sediment core GIK12523-1. 167 records from Plasm bearing foraminifera counts from M35/1_MSN1074. 138 records from Total foraminifera counts of multinet M11/1_MSN520. 892 records from Dinoflagellate cyst counts on sediment core ABC26. 36 records from Phytoplankton abundance in surface water in 2000, Ancon, Peru. 77 records from Distribution of planktonic foraminifera of sediment core SH1972_1. 94 records from Coccolith counts of multinet SO119_MSN1298. 93 records from Ostracoda abundance of Hole 42-372. 2 records from Nannofossil abundance of Hole 9-79A. 2 records from Abundance of broken diatom frustules measured on water bottle samples at station PS58/090-4. 968 records from TTRS Mammals. 42 records from Total foraminifera counts of multinet M12/3_MSN545. 267243 records from Entomological Specimens of Museum of Nature and Human Activities, Hyogo Pref., Japan. 10 records from Large protozoan and small metazoan abundance measured on concentrated water bottle samples at station PS65/593-17. 1970 records from Spores and dinoflagellates of Site 175-1075. 150 records from Phytoplankton abundance at station CD47_0306C#7. 817 records from Phytoplankton abundance during Lev Titov cruise LT90/2. 435 records from Community dynamics in a species-rich patch in the Brazilian Atlantic Forest near Viçosa/MG. 29 records from Nannofossil abundance of Hole 73-523. 71 records from Distribution of benthic abyssal gastropods in the Iberian Deep-Sea Basin (Table 2). 254 records from Grünes Germersheim. 661 records from 녹조류 DB. 10928 records from TRTE Herbarium (TRTE). 130 records from Occurrence of ostracodes in ODP holes 101-627B and 101-635B (Table 1). 2184 records from (Figure 7) Distribution chart of benthic foraminifers in ODP Site 126-793. 36 records from (Table 2) Ostracode distribution in ODP Hole 122-760B. 380 records from Stable oxygen and carbon isotope ratios of Globigerinoides obliquus of quantitative range chart of the ostracodes in the Pliocene-Pleistocene interval of ODP Hole 107-654A. 17 records from (Table 2.2.1.1) Abundance of sympagic meiofauna of sea-ice core IO-13. 105 records from BIRDRACE coesfelder_vogelkundler. 151 records from (Appendix A) Abundance of calcareous dinoflagellates of sediment core GeoB2204-2. 2303 records from Planktic foraminifera abundance in per cent of Hole PRAD1-2. 73 records from Nannofossil abundance of Hole 3-15. 9 records from Nannofossil abundance of Hole 29-277. 6 records from Nannofossil abundance of Hole 10-90. 10 records from Abundance of empty diatom frustules measured on water bottle samples at station PS58/108-1. 1 records from Nothrus echinatus. 169086 records from Estonian Nature Observations Database. 22 records from (Table 2) Species composition of algae and cyanobacteria encountered in plankton of the Large Aral Sea on June 2-8, 2008. 5148 records from Colección de Reptiles - Museo de Herpetología de la Universidad de Antioquia. 4982 records from Registros biológicos de especies de fauna vertebrada terrestre en las centrales de San Carlos y Jaguas - 2007. 2 records from The first record of a fly of the family Milichiidae (Diptera) interacting with an ant of the genus Polyrhachis Smith, 1857 (Hymenoptera: Formicidae). 538 records from Composición florística y estructura de una parcela permanente en bosques húmedos tropicales del municipio de Pie de Pepe, Chocó. 350 records from Record of 7 acritarch taxa, Mg/Ca sea-surface temperatures and palynological preparation data from the Miocene, Pliocene and Pleistocene of DSDP Hole 94-610A. 1 records from Nothrus biurus. 94 records from John Muir Trust - Vascular Plants and Bryophytes of Glen Sligachan. 39 records from Colección de Urocordados. 49637 records from Monitoring data from the federal state Hesse (Germany). 86 records from Alter Kreidebruch Saßnitz/Rügen. 83 records from Birdrace-Die_Vogelscheuchen-Herford. 13 records from Kleinsäuger der Mergelgruben Misburg (Hannover). 163 records from Tiere und Pflanzen am Pfannenbach. 9 records from Phytoplankton abundance at station Casma_2003-03-13_2, Casma, Peru. 3 records from Distribution of meiobenthos in sediment core M19_217-2 (2) of the northeastern Atlantic (Table 1). 8 records from Abundance of radiolaria at station LV28-14-2. 38 records from BB-Biodiversität a. 27 records from Naturgarten Vielfalt - Naturlehrgarten Fa. Dehner. 47 records from Nannofossil abundance of Hole 64-479. 2 records from Nannofossil abundance of Hole 4-26. 78 records from Nannofossil abundance of Hole 27-262. 14 records from Range table from ostracoda in ODP Hole 160-967A. 4 records from Distribution of Quinqueloculina sp. in sediment core 13200-077. 620 records from Lichens of Rocky Seashores. 154 records from Benthic macrofauna abundance of subcores of sediment core 13078-015. 72 records from Planktic foraminifera counts of sediment core V29-30. 900 records from Occurrence of dinoflagellate cysts in ODP Hole 119-738C (Appendix). 146133 records from The Fungal Collection at the Senckenberg Museum für Naturkunde Görlitz. 57 records from Kindervilla Aussengelände/ Hiltroper Park. 1 records from Sungei Buloh - Mangrovenwald. 2073 records from Bryophyte collection of Jyväskylä University Museum. 45 records from Collection Bryozoa - ZIM Hamburg. 200 records from Macrobenthos in surface sediments off Sylt collected during Heincke cruise HE233. 22 records from Crustacea in surface sediments off Sylt collected during Heincke cruise HE278. 1932 records from Benthic and planktonic foraminifera in ODP Hole 123-766A (Table 1-4). 180 records from (Table 7) Distribution of the large, many-chambered Globigerinelloides species in DSDP Hole 79-545. 15 records from (Table T1) Lithology and palynomorphs of neogene sediments of ODP Hole 178-1095B. 170 records from Benthic macrofauna abundance of subcores of sediment core 12930-065. 160 records from Benthic macrofauna abundance of subcores of sediment core 13200-045. 42 records from Planktic foraminifera counts of sediment core ELT48.022-PC. 23 records from Landwehrbach. 104 records from Echinoderms in surface sediments off Sylt collected during Heincke cruise HE241. 976 records from (Table 3) Distribution of dinoflagellate cysts in ODP Hole 103-641A. 84 records from Seawater carbonate chemistry and processes during experiments with phytoplankton Emiliania huxleyi (strain Bergen 2005), 2010. 2267 records from (Table 2) Relative abundance of benthic foraminifera in sediment core CD17-30. 62 records from (Table S1b) Measured tomographic parameters for Oridorsalis umbonatus during the PETM for ODP Site 208-1262. 1011 records from Biodiversidad fitoplanctónica de cenotes: Patrones espaciales y temporales. 813 records from Estudio etnobotánico de las malezas útiles presentes en diferentes agroecosistemas en el municipio de Santa María Tecomavaca, Valle de Tehuacán-Cuicatlán, México. 75655 records from Ibaraki Nature Museum, Vascular Plants collection. 201 records from Mycological collections of the University of Tartu. 2676 records from Abundance of benthic infauna in surface sediments from the North Sea sampled with TYRO in 1986. 432 records from Abundance of large foraminifera in cores from transect HYD-02A, IODP Expedition 325. 844 records from (Table 2) Relative abundance of 13 species of planktonic foraminifers of sediment core GIK17938-2. 750 records from (Table 20) Benthic foraminifera in early Miocene sediments of DSDP Hole 90-594. 4433 records from Röntgenarchiv Wilhelm Stürmer - SMF. 15455 records from Laboratorio de Entomología y Control de Plagas del Instituto Cavanilles de Biodiversidad y Biología Evolutiva de la Universidad de Valencia: ENV. 172 records from (Table 8) Relative abundance of benthic foraminifera in ODP Hole 112-682A, Part I. 3378 records from (Appendix 1) Census data of planktic foraminiferal faunas together with estimates of mean annual SST for DSDP Site 90-594. 613 records from Distribution of dinoflagellate cycst at ODP Site 123-765 (Table 1). 988 records from Managing open habitats for species conservation: the role of wild ungulate grazing, small-scale disturbances, and scale - Corynephorus canescens domiated grassland. 11220 records from (Appendix I) Planktonic foraminiferal biostratigraphy of ODP Hole 113-689B. 4317 records from Flora del Parque Nacional Cumbres de Monterrey, Nuevo León, México. 1200 records from Invertebrate specimens of Toyama Science Museum. 6 records from Description of lithologic section units of IODP Hole 325-M0054B. 280 records from (Table 3) Distribution of Neogene planktonic foraminifers in sediments of ODP Hole 115-705A. 21 records from Description of lithologic section units of IODP Hole 325-M0042A. 61839 records from Herbarium Senckenbergianum (FR) - Fungi. 54138 records from Flora Mycologica Iberica. 7664 records from National Institute of Marine Sciences and Technologies - Trawl Surveys (AfrOBIS). 49406 records from Marine and Coastal Management - Linefish Dataset (Second Semester of 1985) (AfrOBIS). 11926 records from Crispin S. Guppy Collection. 23 records from AlgaTerraMovies. 433463 records from Israel Nature and Parks Authority. 2 records from ZFMK Heteroptera collection. 117 records from (Table T1) Nannofossil abundance of volcaniclastic and other lithologies from ODP Hole 197-1203A. 1271 records from Distribution of planktonic foraminifera of sediment core Core190. 82 records from Mainfränkischer Trockenrasen und Naturschutzgebiet Höhfeldplatte bei Veitshöchheim. 8 records from Crustacea in surface sediments off Sylt collected during Heincke cruise HE206. 3968 records from (Appendix A) Abundance of benthic foraminifera in sediment core GIK17940-2. 20 records from (Table 2c) Nannofossil distribution chart of ODP Hole 122-762C. 929 records from Flora acuática vascular de las regiones hidrológicas R66 (Lagos Cráter del Nevado de Toluca) y R67 (Río Amacuzac-Lagunas de Zempoala), México. 1871 records from Registros biológicos de especies de fauna vertebrada terrestre en la central hidroeléctrica Miel I - 2009. 342 records from The Deepwater Program: Northern Gulf of Mexico Continental Slope Habitat and Benthic Ecology - DgoMB: Fish. 31157 records from Marine and Coastal Management - Linefish Dataset (Second Semester of 2003) (AfrOBIS). 7290 records from Rosaceae and Fabaceae of Kevo region, Northern Finland. 23769 records from Distribution of planktic foraminifera in surface sediments of the Atlantic Ocean. 2455 records from Herbarium BSG Bryophyta. 420 records from (Table 4) Relative abundances of planktonic foraminifera in Pliocene sediments of ODP Site 161-975 in the Mediterranean Sea. 156 records from Schulgelände Dientzenhofer-Gymnasium (Bamberg). 24 records from Occurrence of mammalia relicts at site Bivak Cave. 12 records from Planktic foraminifera abundance of Hole 14-138. 2310 records from (Table 15A) Occurrences of planktonic foraminifers in selected samples of DSDP Hole 90-593. 8 records from Planktic foraminifera abundance of Hole 54-420. 32 records from The Deepwater Program: Northern Gulf of Mexico Continental Slope Habitat and Benthic Ecology - DgoMB: Invertebrates. 1678 records from Agriculture and Agri-Food Canada, St. Johns, Newfoundland. 191859 records from herbario. 11 records from IPK Genebank. 615 records from Distribution of lithic fragments and the planktic foraminifera Neogloboquadrina pachyderma in quaternary sediments of DSDP Hole 94-609 (Table 2). 2 records from uno city. 23 records from Microplankton abundance in the euphotic zone of the Aegean Sea in September 1998. 20 records from Occurrence of mammalia relicts at site Kesslerloch. 10 records from Occurrence of mammalia relicts at site Adler Cave xx. 66 records from Abundance of radiolaria in surface sediment, Sea of Okhotsk. 2 records from Planktic foraminifera abundance of Hole 28-267. 1 records from Planktic foraminifera abundance of Hole 28-274. 364 records from Foraminifera abundance of Hole 60-455. 102 records from (Table 5) Planktonic foraminifer species distribution, abundance, and preservation in DSDP Site 92-600. 528 records from Range table from planktonic foraminifers in ODP Hole 141-860B. 33 records from Range table from planktonic foraminifers in ODP Hole 141-861B. 196 records from Range table from planktonic foraminifers in ODP Hole 162-986D. 92 records from Range table from planktonic foraminifers in ODP Hole 167-1017B. 25 records from Nannofossil abundance of Hole 10-94. 469 records from Benthic foraminifera abundance of Hole 73-523. 77 records from Benthic foraminifera abundance of Hole 84-567. 2 records from Benthic foraminifera abundance of Hole 42-373A. 1115 records from Distribution of planktic foraminifera (200-630 µm) of sediment core M8_057-2 (Table 4). 89918 records from FloVegSI - Floristical and fitocenological database of ZRC SAZU. 918 records from Invertebrate survey, Heard Island 2001. 41 records from Altholzparzelle Eilenriede Hannover. 44 records from Leegmoor (Moormerland/Leer). 135 records from Birdrace_Dith_MarshSandpiper-Dithmarschen. 26 records from Microplankton abundance at Station MARCH-1997-GN36199704603MNB04 in the euphotic zone of the Aegean Sea in spring 1997. Part 3 - coccolithophores and other groups. 49 records from Occurrence of mammalia relicts at site Felsställe. 10 records from Planktic foraminifera abundance of Hole 6-47A. 22 records from Planktic foraminifera abundance of Hole 18-174. 182 records from Planktic foraminifera abundance of Hole 21-203. 1195 records from Range table from planktonic foraminifers in ODP Hole 161-975B. 218 records from Range table from planktonic foraminifers in ODP Hole 180-1115C. 21 records from Range table from planktonic foraminifers in ODP Hole 183-1135A. 9 records from Range table from benthic foraminifers in ODP Hole 178-1103A. 226 records from Range table from dinoflagellates, acritarchs and prasinophytes in ODP Hole 159-959D. 92 records from Range table from dinoflagellates, acritarchs and prasinophytes in ODP Hole 160-969A. 1312 records from (Table 3) Distribution of benthic foraminifers in the > 63 µm fraction in surface sediments from the central Arctic Ocean. 7457 records from Distribution of dead benthic foraminifera in surface sediments of the Norwegian Sea (Table 3). 44 records from Flora und Fauna in unserer Kita. 107485 records from Botany Division, Yale Peabody Museum. 1201 records from Collection Paläobotanik SMB. 2 records from Abundance of benthos infauna at station GIK23025-2. 46 records from Effects of varying food-availability on ecology and distribution of smallest benthic organisms in sediments of the arctic Fram Strait during POLARSTERN cruise ARK-XV/2. 12 records from Range table from planktonic foraminifers in ODP Hole 182-1134B. 3387 records from Sand flies of Eastern Africa. 565 records from Marine palynomorph abundance estimates of sediment core CRP-2A (Fig. 2). 78 records from Rössewiesen am Krumbholz. 17964 records from Ornithology Collection. 100 records from Mean density of total metazoan meiofauna and major taxa or groups in the top 10 cm of surface sediment on 25 different dates at DYFAMED station. 144 records from Taxonomy of the South American genus Pachypops Gill 1861 (Teleostei: Perciformes: Sciaenidae), with the description of a new species.. 15975 records from condoncollection. 84 records from (Table 10) Distribution of coccoliths in Core AMK7-734 from the Tajura Rift. 205 records from Nottinghamshire Biological and Geological Records Centre - NBGRC Crayfish Dataset. 5426 records from Collection Francaise de Bacteries Phytopathogenes. 377420 records from EcoRecord - Vascular plant records held by EcoRecord for the Birmingham and the Black Country area collated prior to March 2013. 5263 records from Colección Herpetológica (anfibios) de la Universidad Industrial de Santander. 10175 records from Seil Natural History Group - SNHG Biological Records Dataset. 56 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Rheidae. 19 records from A new species of Anabarhynchus (Diptera: Therevidae) from an ocean beach in south east Victoria. 222 records from (Table 3) Composition of turbidite and background samples at ODP Site 166-1003. 94 records from (Appendix 4) Calcareous nannofossils in ODP Hole 113-689B. 54179 records from E. C. Smith Herbarium (ACAD). 875 records from John Muir Trust - Plants, Bryophytes and Lichens recorded on the Sandwood Estate during 1998 â 2006.. 4475 records from Coleoptera collection (EC) of the Muséum national d'Histoire naturelle (MNHN - Paris). 36115 records from Colección Nacional de Invertebrados - Museo Argentino de Ciencias Naturales 'Bernardino Rivadavia'. 163 records from Dinoflagellate cysts of ODP Hole 189-1172D. 3 records from Dinoflagellate abundance of Hole 85-572. 50 records from Phytoplankton abundance and species composition in the Gulf of Naples in June 1999 at station MCSSII-phyto120-128. 50 records from Abundance of birds on the channels of Lena Delta in the nesting period. 217 records from 5.Tag der Artenvielfalt: Thema Stadtbiotope. 5588 records from Snow Petrel nest census, Mawson region 2004/05. 142 records from Benthic meiofauna abundance in surface sediment of core PLG93_BCORE3. 763 records from Bisons Collection. 33 records from Three new species of Gastromyzon (Teleostei: Balitoridae) from the Temburong River basin, Brunei Darussalam, Borneo.. 1781 records from Soft Wheat French National Collection. 194 records from (Table S2) Coccolithophora in sapropel S1 of ODP Hole 160-964B, filtering preparation. 15 records from A survey of the family Carabodidae C. L. Koch, 1836 (Acari: Oribatida), II. 1391 records from Open Mosaic Habitat Survey Group - Plants recorded during Open Mosaic Habitat survey in England and Wales (2012). 9 records from Two new species of Elacatinus (Teleostei: Gobiidae) from the Mexican coast of the Gulf of Mexico.. 2962 records from Alterra (NL) - Microarthropods inventory in calcareous grasslands. 11451 records from NCSM Invertebrate Paleontology Collection. 1 records from Murcia acuminata. 433 records from Caracterización de las coberturas vegetales en el gradiente altitudinal Páramo-Bosque en los complejos de Páramo de Guerrero y Altiplano Cundi-boyacense. 19 records from Scottish Wildlife Trust - Small Cow-wheat distributions for Scotland 1999 to 2005. 121 records from A second update to the checklist of Finnish long-legged flies (Diptera: Dolichopodidae), with a re-evaluation of the status of Hydrophorus callosoma Frey, 1915. 36 records from Pseudolaguvia ferula, a new species of sisoroid catfish (Teleostei: Erethistidae) from India.. 6896 records from Registros de hongos en áreas protegidas de la Argentina. 2423 records from SANT-Bryo. 206 records from Herbarium BSG Hepaticopsida. 413272 records from DATAVES. 1390 records from (Appendix 1) Calcareous nannofossils in ODP Hole 119-738B. 5920 records from Alterra (NL) - Microarthropods inventories by Henk Siepel on various locations. 39 records from Red list project inventory, fungi. 16 records from Inventario de Murciélagos Floreña I, Yopal, Casanare. 53209 records from SysTax - Herbaria. 6887 records from (Figure 13) Distribution of middle Miocene through middle Pleistocene planktonic foraminifera in ODP Hole 132-810C. 1387717 records from Fishbase. 1210 records from Abundance of megabenthic species in trawl catches per station in addition to table 2 during POLARSTERN cruise ARK-VIII/2 (EPOS). 149 records from (Appendix A) Palynofacies raw counts of DSDP Hole 38-338. 150 records from Abundance of phytoplankton, heterotrophic nanoflagellates and bacteria through the water column at time series station L4 in the Western English Channel in 2011. 270 records from Meiofaunal abundance in sediments obtained during RRS Charles Darwin cruise CD179. 6774 records from Colección Nacional de Paleopalinología - Museo Argentino de Ciencias Naturales 'Bernardino Rivadavia'. 637 records from Fossil occurrence from planktonic foraminiferas from IODP Hole 315-C0002B. 923 records from Colección Plantas Vasculares - Herbario del Departamento de Biología, Bioquímica y Farmacia de la Universidad Nacional del Sur. 28 records from The land crab Johngarthia planata (Stimpson, 1860) (Crustacea, Brachyura, Gecarcinidae) colonizes human-dominated ecosystems in the continental mainland coast of Mexico. 88 records from Birdrace_Die_Polyglotten-Saarlouis. 37 records from Berlin - Treptower Park / Karpfenteich. 155 records from Bammentaler Duft- und Heilkräutergarten. 12 records from Anatomical investigation of the slender catshark Schroederichthys tenuis Springer, 1966, with notes on intrageneric relationships (Chondrichthyes: Carcharhiniformes: Scyliorhinidae).. 36 records from Mittelriede Höhe Gliesmarode-Braunschweig. 261 records from (Table 1) Neogene benthic foraminiferal community at DSDP Hole 95-612. 1444609 records from Rotherham Biological Records Centre - Rotherham Biological Records Centre - Non-sensitive Records from all taxonomic groups. 1808 records from University of Amsterdam (NL) - Páramo vegetation research, Ecuador.. 145 records from (Tab. 9.B) Presence and abundance of benthic fauna at station FINO 1 in 2005-2007. 1 records from On the morphology, biometry and biogeography of Lamtopyxis callistoma ( Amoebozoa : Arcellinida ). 1854895 records from Vascular plants in Denmark recorded under the The Nationwide Monitoring and Assessment Programme for the Aquatic and Terrestrial Environments (NOVANA). 18 records from Fossil occurrence from planktonic foraminiferas from IODP Hole 315-C0001I. 51900 records from Thames Valley Environmental Records Centre - Local Wildlife Site Surveys Berkshire. 841 records from Dorset Environmental Records Centre - Dorset Invasive Alien Plants - NBN South West Pilot Project Case Studies. 1 records from Myriopoden von Epirus. 68 records from Late Pleistocene planktonic foraminifera of Hole 302-M0004C (Addendum 1). 69 records from (Table 11) Distribution of coccoliths along Core AMK7-786 from the Tajura Rift. 210 records from (Table 2) Neogloboquadrina plexus coiling direction at DSDP Site 49-410 and Holes 81-552A, 94-610E, and 94-611C. 3313 records from Dorset Environmental Records Centre - Bryophyte Survey of the Poole Basin Mires - NBN South West Pilot Project Case Studies. 40 records from Phytoplankton abundance and species composition in the Gulf of Naples in June 1999 at station MCSSII-phyto102-110. 212 records from (Appendix A) Campanian-Maastrichtian calcareous nannofossils in DSDP Hole 44-390A. 613 records from Countryside Council for Wales - Shad Monitoring data. 252125 records from Moths Ireland. 2052 records from Angelo State Natural History Collections (ASNHC) - Ornithology Collection. 342 records from Kremmer Luch. 172 records from Leben im Finkensteiner Moor. 23 records from Assemblage of living benthic foraminifera in sediment core SO129_MC-03, >125 µm fraction. 25 records from Assemblage of total living benthic foraminifera in sediment core SO117_MC464. 2464 records from Benthic foraminiferal abundances at the Cretaceous/Paleogene boundary of ODP Hole 117-1049C at Blake Nose, Northwest Atlantic (Appendix A). 143 records from Total foraminifera counts of multinet M12/3_MSN535. 24 records from Content of coarse fraction and G. menardii in sediment corev V25-43. 6 records from Large protozoa abundance measured on concentrated water bottle samples at station PS58/014-6. 24 records from Abundance and carbon biomass of phytoplankton at station TT008_5-CTD22. 18 records from Abundance, biovolume and biomass of heterotrophic dinoflagellates at station TT007_8-CTD102. 6 records from Microzooplankton abundance and biomass at station NBP97-08-35-5. 12 records from Phytoplankton abundance in surface water in 1993, Ancon, Peru. 8 records from Phytoplankton abundance at station Casma_2003-02-27_1, Casma, Peru. 42920 records from Royal Horticultural Society - RHS monitoring of native and naturalised plants and animals at its gardens and surrounding areas. 28 records from Meiofauna abundances at the Arctic Håkon Mosby Mud Volcano (HMMV) of sediment core PS64/390-1c. 117 records from Streuobstwiese Stedar 2009. 1864 records from Museu de Ciències Naturals de Barcelona: MCNB-Tissue. 27 records from Smear slide analysis on sediment core GeoB4212-2. 26 records from Coccolith counts of multinet M32/5_MSN988. 137 records from Nanoplankton abundance at station GeoB2008-4. 8 records from Nannofossil abundance of Hole 64-477. 7 records from Nannofossil abundance of Hole 9-78. 30 records from Nannofossil abundance of Hole 29-281. 376 records from Absolute abundance of dead benthic foraminifera of sediment core M5/2_91MC. 16 records from Assemblage of living benthic foraminifera in sediment core SO117_MC464, 63-125 µm fraction. 34 records from Marine Conservation Society - Palinurus elephas or Crawfish sightings in the UK and Ireland from 1969 to the present time.. 49 records from Total foraminifera counts of multinet M42/3_MSN1367. 90 records from Plasm bearing foraminifera counts of multinet M21/2_MSN648. 199 records from Palynomorpha in sediment core PM9462-4 from the Laptev Sea. 1308 records from Dinoflagellate cysts counts of sediment core MD95-2010. 19 records from Abundance, biovolume and biomass of heterotrophic dinoflagellates at station TT011_7-CTD84. 24 records from Abundance, biovolume and biomass of heterotrophic dinoflagellates at station TT012_5-CTD85. 1 records from Microplankton counts and carbon biomass at station TT011_15-CTD168. 3 records from Sarcodine counts and carbon biomass at station TT007_12-CTD145. 109 records from ZFMK AMIBIO. 12 records from Phytoplankton abundance at station Sechin_2003-09-18_2, Casma, Peru. 9 records from Nematode genera abundances at the Arctic Håkon Mosby Mud Volcano (HMMV) of sediment core PS64/312-1. 17 records from Meiofauna abundances at the Arctic Håkon Mosby Mud Volcano (HMMV) of sediment core PS64/321-1. 19 records from Meiofauna abundances at the Arctic Håkon Mosby Mud Volcano (HMMV) of sediment core PS64/362-1. 1257 records from (Table A.01) Planktic foraminiferal census data of sediment core GIK23414-7. 5 records from Wanninchen. 9 records from Coccolith counts of multinet M32/5_MSN981. 318 records from Geometry of coccolith Coccolithus pelagicus in ODP Hole 104-643A. 95 records from Nannofossil abundance of Hole 15-149. 588 records from (Table 5) Foraminiferal numbers of empty test of important species in surface sediments. 181 records from Total foraminifera counts from multinet M31/3_MSN914. 132 records from Plasm bearing foraminifera counts of multinet M21/1_MSN613. 37 records from Plasm bearing foraminifera counts of multinet M27/2_MSN879. 110 records from Total foraminifera counts of multinet PO247/2_MSN1375. 1 records from Microzooplankton abundance and biomass at station TT050_25-4. 14 records from Phytoplankton abundance at station Sechin_2003-09-18_1, Casma, Peru. 22 records from Phytoplankton abundance in surface water in January 2007, Sechura Bay, Peru. 4 records from Wälder und Seen rund um den Mühlenberg. 2 records from MfN - Glacial erratics. 2 records from Nannofossil abundance of Hole 9-82. 2 records from Nannofossil abundance of Hole 94-610. 271 records from Planktic foraminifera counts of sediment core RC11-147. 33403 records from Colección de Entomología del Museo de Ciencias Naturales de Tenerife: TFMC-EN. 583 records from Macrobenthos in surface sediments off Sylt collected during Heincke cruise HE262. 3726 records from (Table 3) Relative abundance of benthic foraminifera in sediment profile HUD84-030-04. 196 records from (Table 2) Distribution of planktonic foraminifera shells of different species in deposits from DSDP Hole 30-289. 117 records from (Table 2) Distribution of calcareous nannofossils in ODP Hole 113-690C. 6414 records from Colección de referencia de vectores de Leishmania spp (causante de Leshmaniasis cutánea localizada) de la Península de Yucatán y un estudio preliminar en un área endémica de Quintana Roo. ECOSUR_SNIB. 7 records from Collection Malakologie - SMNG. 16118 records from Database of Fungal Specimens Maintained at the Selected Japanese Herbaria. 8 records from Microfossil abundance of Hole 16-157A. 8 records from Nannofossil abundance of Hole 49-412A. 8 records from Phytoplankton abundance measured on water bottle samples at station PS65/545-1. 63 records from Planktic foraminifera counts of sediment core V19-21. 1343 records from Bryophyte specimens of Iwate Prefectural Museum. 22419 records from The Fungal and Lichen Collections at the Herbarium Marburgense. 150 records from (Table 3) Numerical abundances of nannofossil taxa in ODP Hole 126-791A. 48 records from Crustacea in surface sediments off Sylt collected during Heincke cruise HE275. 1188 records from (Table 15) Distribution of planktonic foraminifers in ODP Hole 108-666A. 128 records from Pliocene/Pleistocene benthic foraminiferal abundances from ODP Hole 172-1055B. 2315 records from (Fig. 5) Distribution of benthic foraminifera in sediment profile GeoB9526. 1353 records from (Table 2) Distribution of planktonic foraminifera in the upper Turonian-lower Campanian succession in ODP Hole 122-763B, Part I. 571 records from Catálogo de autoridad taxonómica del género Quercus, Fagaceae en México. 3422 records from Colecta botánica: área maya región de la Reserva Calakmul, Campeche. 115280 records from Dataflos. 1618 records from Abundance of benthic infauna in surface sediments from the North Sea sampled during two Michael Sars cruises in 2000. 6006 records from (Table 5) Distribution of benthic foraminifers in the late Cretaceous of DSDP Hole 71-511. 21348 records from Phytopathogenic Fungi Observed by Hans and Hanna Doppelbaur. 5231 records from The Myxomycetes Collections at the Botanische Staatssammlung München - Collection of Martin Schnittler. 98709 records from USU-UTC Specimen Database. 1997 records from Lichen collection. 19903 records from HBGSpermatophyta - Herbarium Hamburgense. 108 records from BIRDRACE Diesmal sehen wir mehr. 17 records from Nannofossil abundance of Hole 85-572D. 43 records from Nannofossil abundance of Hole 11-102. 64 records from Range table from ostracoda in ODP Hole 151-910C. 7 records from Diatom abundance measured on water bottle samples at station PS58/107-5. 1966 records from Relative abundance of Neogene nannofossils at ODP Site 165-999 from the Caribbean. 4 records from Distribution of Quinqueloculina sp. in sediment core 13077-019. 5 records from Distribution of Quinqueloculina sp. in sediment core 13200-039. 21 records from Meiofauna abundance in sediment core 54301-010. 13 records from Benthic macrofauna abundance of sediment core 12930-048. 131 records from Dinoflagellate cysts from sediment core PS2757-8. 9660 records from (Table 3) Ranges of upper Eocene Holocene planktonic foraminifera in ODP Hole 119-744A. 1250 records from Colección de Crustáceos Macrobénticos del Golfo de México (ICMyL-DF, UNAM). 5 records from Regenwasserabfangbecken Erlenbach. 1000 records from Diplopoda (JJHA-DI). 162 records from Antarctic fish Gobionotothen gibberifrons. 394 records from (App 7) Relative contents of benthic foraminifera species in sediments accumulated during last 1000 years, Core ASV11-987. 125 records from (Figure 10) Concentrations and accumulation rates of Uvigerina spp. from ODP Hole 175-1086A. 33 records from (Appendix 2) Abundances of Neogloboquadrina pachyderma and ice-rafted debris in sediment core SU81-18. 2019 records from (Table 7) Distribution of dead benthic foraminifera in deep-sea surface sediments of the Scotia Sea, part 2. 62 records from Lebensraum Dorf. 2785 records from (Appendix 2, Part 3) Distribution of Eocene to Recent benthic foraminifera in ODP Site 113-690. 1601 records from Respaldo de las colecciones de tejidos del Museo de Zoología, Departamento de Biología Evolutiva, Facultad de Ciencias, UNAM (Herpetofauna). 36 records from (Table 2) Distribution of early late Eocene fossil content in ODP Hole 115-714A. 675 records from (Table 9) Distribution of Neogene planktonic foraminifers in sediments of ODP Hole 115-711A. 488 records from Relative abundance of ostracods in sediment core Oh09. 154124 records from Arizona State University Lichen Collection. 1000 records from Plant Specimens of Taga Town Museum, Shiga Pref., Japan. 1110 records from MEXU/Colección Histórica. 6 records from Sediment properties of core CD86_11_BC8. 350 records from Orchideenstandort Nostengraben - Kretzberg (Oßmaritz). 16 records from Phytoplankton abundance during Professor Siedlecki cruise PSied90/1. 12 records from Occurrence of mammalia relicts at site Trafalgar Square. 16 records from Occurrence of mammalia relicts at site Buchenloch. 1 records from Oribates ovalis. 268160 records from Plantae, TAIF (Taiwan e-Learning and Digital Archives Program, TELDAP). 15 records from Planktic foraminifera abundance of Hole 1-6. 4756 records from (Table 8A) Occurrences of planktonic foraminifers in selected samples of DSDP Hole 89-586B, Sections 1-1 through 5-1. 27 records from Planktic foraminifera abundance of Hole 51-417B. 17400 records from Sam Mitchel Herbarium of Fungi (Denver Botanic Gardens). 328 records from Range table from planktonic foraminifers in ODP Hole 170-1040C. 2922 records from National Lesser Horseshoe Bat Database. 1040 records from Foraminifera and ostracods profile from sediment core AV14_K2-3. 855 records from (Table T7) Planktonic foraminifera stratigraphy of ODP Hole 198-1210A, Zones Palpha-P3b. 100733 records from South African Institute for Aquatic Biodiversity - Fish Collection (AfrOBIS). 8684 records from Individual Sightings. 30625 records from Kochi Prefectural Makino Botanical Garden. 1656 records from Relative abundance of planktic foraminifera in the 120 kyr time slice reconstruction of sediment core RC11-86. 5 records from Analyses of the recent components in the sand fraction of sediment core PS1400-4. 242 records from (Fig. 3) Age and multiproxy studies of sediment core GeoB7186-3. 879 records from (Table 1) Relative abundance of planktic foraminifera at DSDP Site 48-401 from the Bay of Biscay, North Atlantic. 111 records from Landesweite NABU-Vogelrallye. 12 records from Microplankton abundance in the euphotic zone of the Aegean Sea at Station JUNE-1998-IR72. 14 records from Occurrence of mammalia relicts at site Crumstadt 1. 563 records from Foraminifera abundance of Hole 74-526A. 25 records from Description of three new species of the genus Chromaphyosemion Radda, 1971 (Cyprinodontiformes: Nothobranchiidae) from the coastal plains of Cameroon with a preliminary review of the Chromaphyosemion splendopleure complex.. 358 records from Benthic foraminifera and algae abundance of Hole 81-554A. 60 records from Range table from benthic foraminifers in ODP Hole 182-1128C. 13239 records from Collection Bryozoa SMF. 299 records from (Table S3) Relative abundance of coccolithophora in sapropel S1 of ODP Hole 160-964B, smear slide counts. 33 records from A redescription of the species of Eupolybothrus Verhoeff s. str. preserved in the British Museum (Natural History) and the Hope departement of Zoology Oxford (Chilopoda Lithobiomorpha). 3321 records from The Pisces Collection at the Staatssammlung für Anthropologie und Paläoanatomie München. 4801101 records from Botanical Society of the British Isles - Vascular Plants Database additions since 2000. 195264 records from U.S.D.A. Forest Service, Redwood Sciences Laboratory - Lamna Point Count. 337 records from Zooplankton of the Eastern South Pacific, Universidad de Guayaquil, Ecuador (OBIS South America, SOUTH PACIFIC NODE). 169 records from Sediment components of core L008/23. 655 records from Planktic foraminifera assemblage in sediment core GIK17049-6. 5566 records from Colecciones de George Boole Hinton depositadas en el herbario de Kew: Familia Leguminosae. 1644 records from Bohart Museum of Entomology, UCD. 212 records from Am Moosangerweg. 99 records from Wiese und Weide am Waldrand von Gusterath. 211 records from Stadt Königs Wusterhausen. 595 records from Freigelände Naturschutzscheune Reinheimer Teich (Kreis Darmstadt-Dieburg). 54 records from Artenvielfalt im Umfeld der Burgwegschule. 167 records from Birdrace-Nord_Seh_Team-Nordfriesland. 234 records from Occurrence of mammalia relicts at site Pestera Cioarei. 6 records from Occurrence of mammalia relicts at site Magdalenhöhle. 20 records from Occurrence of mammalia relicts at site Felslindlhöhle. 1 records from Planktic foraminifera abundance of Hole 8-71. 11 records from Planktic foraminifera abundance of Hole 47-398B. 692 records from Planktic foraminifera abundance of Hole 40-360. 553 records from Planktic foraminifera abundance of Hole 68-503A. 7530 records from (Table 3) Distribution and abundance of selected planktonic foraminifera of the Pliocene DSDP Hole 41-366A. 297 records from Foraminifera abundance of Hole 60-454A. 817 records from Planktic foraminifera abundance of Hole 37-332A. 3719 records from (Figure 4) Stratigraphic distribution of planktonic foraminifera in DSDP Hole 93-604. 10 records from Planktic foraminifera abundance of Hole 15-154A. 84 records from Streuobstwiese Haus Zeitz. 35 records from Aves Argentinas / Asociación Ornitológica del Plata - Conteo anual de chorlos de pastizal en Argentina - Campaña marzo 2007. 369 records from Planktic foraminifera abundance of Hole 24-238. 1741 records from Amphibian observations from Nida Valley. 98 records from Range table from planktonic foraminifers in ODP Hole 177-1089B. 35 records from Range table from benthic foraminifers in ODP Hole 181-1124C. 3 records from Dinoflagellates, pollen and spore abundance of Hole 29-284. 1998 records from Table A3. Benthic foraminifera assemblage of sediment core GeoB1710-3. 142 records from (Table 3) Distribution of benthic foraminifers in middle Miocene sediments of ODP Hole 182-1134A in the Great Australian Bight. 404842 records from Texas A&M University Insect Collection. 1 records from Abundance of benthos infauna at station GIK23060-1. 5722 records from Insect Arthropods (KIDR-IN). 8 records from Revision of the ant genus Anillomyrma Emery, 1913 (Hymenoptera: Formicidae: Myrmicinae: Solenopsidini).. 1 records from Nothrus sinuatus. 20381 records from MSB Host Collection (Arctos). 1 records from Il popolamento dell'Appennino meridionale: dall'Appennino campano alle serre calabre. Osservazioni sui chilopodi dell'Appennino lucano e calabrese (Chilopoda). 766 records from Reptiles and Amphibians Distribution Atlas 1978 (An Foras Forbartha). 4 records from Four new species of deep-water catsharks of the genus Parmaturus (Carcharhiniformes: Scyliorhinidae) from New Caledonia, Indonesia and Australia.. 4 records from (Table 1) PBDE and BDE congener concentration in adipose tissue of East Greenland polar bears collected 1999-2001. 5 records from The tip of the iceberg: a distinctive new spotted-wing Megaselia species (Diptera: Phoridae) from a tropical cloud forest survey and a new, streamlined method for Megaselia descriptions. 502 records from (Appendix A) Planktonic foraminifera abundances in ODP Site 130-806B. 41 records from Two new species of Pseudoscopelus (Teleostei: Chiasmodontidae), with a new diagnosis for the genus.. 6 records from Range table from planktonic foraminifers in ODP Hole 171-1049B. 72 records from Range table from benthic foraminifers in ODP Hole 172-1060B. 1 records from Range table from benthic foraminifers in ODP Hole 188-1165A. 4 records from Dinoflagellate abundance of Hole 14-135. 30 records from Range table from dinoflagellates, acritarchs and prasinophytes in ODP Hole 151-913B. 876 records from Phytoplankton abundance in surface water in July-August 1996, Ilo, Peru. 126 records from Tag der Artenvielfalt mit SchülerInnen des Leibniz-Gymnasiums in Neustadt a.d.W.. 65704 records from Coleoptera. 2 records from Eine neue Art der Gattung Suctobelba Paoli (Suctobelba vera n. sp.) aus Deutschland (Acarina: Oribatei). 8 records from A new species of Orthosiphon (Lamiaceae) from Angola. 3027 records from Fungi Collection in BCRC. 26990 records from British Lichen Society - BLS Rare and Threatened Lichen Records: England. 17 records from Inventarios de Herpetos de la Microcuenca de la Quebrada Agua Blanca, Vereda Marroquín, Yopal, Casanare. 37 records from Description of a new species of catshark, Atelomycterus marnkalha n. sp. (Carcharhiniformes: Scyliorhinidae) from north-east Australia.. 21 records from (Table 8) Pleistocene nannofossil range chart for ODP Hole 134-833A. 84 records from (Table 3) Minerals, and calcareous and siliceous fossil residues from DSDP Hole 93-603. 3504 records from Alterra (NL) - Entomofauna inventory in Amerongen forest. 1596 records from (Figure 5) Planktonic foraminifera distribution in ODP Hole 101-628A. 1186 records from Inventarios de Fauna y Flora en Relictos de Bosque en el Enclave Seco del Río Amaime, Valle del Cauca. 18 records from Rita macracanthus, a new riverine catfish (Teleostei: Bagridae) from South Asia.. 124 records from Range table from benthic foraminifers in ODP Hole 189-1171A. 47 records from A preliminary inventory of the catfishes of the lower Rio Nhamundá, Brazil (Ostariophysi, Siluriformes). 2 records from (Table 4) Differences in king penguin (Aptenodytes patagonicus) colony arrivals and departures based on age, Possession Island. 2046 records from (Table T3) Benthic foraminfera stratigraphy of ODP Hole 199-1221C sediments. 25 records from Inventario de Murciélagos Buenos Aires, Tauramena, Casanare. 589 records from (Table 12) Distribution of benthic foraminifera in bottom sediments of the Lazarev Sea. 81 records from Aves del Santuario de Fauna y Flora Malpelo entre 2006 y 2013. 198566 records from Naturalis Biodiversity Center (NL) - Botany Utrecht. 105 records from Natural England - Species Surveillance Project - In-House Pilots records for 2012. 408 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Columbidae. 2494 records from Marine Environmental Monitoring - Marine Turtles. 360 records from (Figure 1g) Distribution of planktonic foraminifera in bottom sediments of Core Vy20-3174. 607 records from Líquens d'Andorra. 43 records from Saalewiesen Naumburg. 100 records from Birdrace-ImmerWiederhopf-Lörrach. 89 records from Schulgelände Paul-Gerhardt-Schule. 161 records from BIRDRACE Nord-Seh-Team. 3570 records from Total fauna of benthic foraminifera of sediment core Kronsmoor, Late Cretaceous. 9 records from Assemblage of living benthic foraminifera in sediment core CD146_55921#1, >150 µm. 116 records from Total foraminifera counts of multinet M42/3_MSN1362. 8778 records from Collection Herpetology SMF. 183 records from (Table 2) Mollusc biostratigraphy of facies underlying the 'Braunkohlensande' in the Lauenburg district, north Germany. 1 records from Arthropoden aus südostalpinen Höhlen.. 27988 records from Argyll Bird Club - Bird records for Argyll for the years 2002 and 2003. 2661 records from Composición florística y estructura de una parcela permanente en bosques secos tropicales del Parque Nacional Natural Tayrona. 457 records from Microbial Observatory of the Laboratoire Arago. 1300 records from Composición florística y estructura de una parcela permanente en bosques húmedos tropicales del río Cajambre (Guandal), municipio de Buenaventura, Valle del Cauca. 142691 records from Vascular Plants, Field notes, Agder naturmuseum (KMN). 216 records from (Table A2) Stratigraphic distribution of major planktic foraminifer species of ODP Hole 198-1210A. 1715 reco
Keywords: GBIF; biodiversity; species occurrences